3-5 mu m mid-infrared all-fiber laser all-oxide thin film and preparation method
Patent Information
- Application Number
- CN202611102247.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-30
AI Technical Summary
因此,现有多层膜结构无法直接迁移应用于本发明的中红外全光纤激光器端面集成场景,亦无法解决本发明所面临的热效应、环境稳定性及高功率运行等关键技术难题
1、五层功能分层集成架构,实现端面一体化多功能协同,支撑全光纤谐振腔集成:
Smart Images

Figure CN123018545A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optical thin film technology, and in particular to a 3-5μm mid-infrared all-fiber laser all-oxide thin film and its preparation method. Background Technology
[0002] Mid-infrared fiber lasers (3-5 μm) have significant applications in gas detection, infrared countermeasures, medical surgery, and environmental monitoring due to their coverage of numerous molecular vibrational and rotational absorption lines and low atmospheric transmission loss. Compared to chemical and gas lasers, fiber lasers offer advantages such as compact structure, superior beam quality, excellent heat dissipation, and high system stability. They represent a key technological route for the miniaturization, engineering, and long-term stable operation of mid-infrared lasers, making performance enhancement and system integration a current research hotspot.
[0003] From the perspective of system operation characteristics, mid-infrared fiber lasers, limited by their energy level structure and pumping method, have relatively low electro-optical conversion efficiency and are prone to generating a large amount of heat. This heat tends to accumulate at key optical components of the resonant cavity (especially the end-face reflection structure), causing changes in refractive index, beam distortion, and intracavity mode instability, which in turn leads to output power temperature drift, beam quality degradation, and even device failure. Simultaneously, the resonant cavity loss directly determines the laser's start-up threshold and slope efficiency. Any unnecessary absorption, scattering, or transmission losses will be converted into additional heat sources. Even a slight decrease in the reflectivity of a high-reflectivity cavity structure can significantly affect laser performance and operational stability. Traditional high-power laser systems often suppress thermal effects through complex heat dissipation structures such as water cooling or forced air cooling. This not only increases system size, complexity, and manufacturing costs but also hinders the miniaturization, integration, and long-term stable operation of lasers.
[0004] For mid-infrared fiber lasers in the 3-5μm band, all-fiber integration is the core approach to improve system stability, resistance to environmental disturbances, and integration. However, due to limitations in the properties of mid-infrared fiber materials and device fabrication processes, the resonant cavities of existing systems still rely on fiber gratings, end caps, or bulk cavity mirrors. Bulk cavity mirrors require the introduction of free-space coupling structures, significantly increasing system size and adjustment complexity. End cap and fiber grating solutions suffer from insufficient thermal stability, end-face deformation, and long-term reliability degradation under high-power operation. These factors all constrain the development of mid-infrared fiber lasers towards high integration and all-fiber integration. Furthermore, fluoride fibers above 3μm are extremely sensitive to moisture, and their end faces are prone to deliquescence and contamination, leading to optical performance degradation and even device failure. Existing protection solutions mostly rely on gas drying, end cap fusion, or complex packaging structures, which are not only costly but also difficult to integrate with all-fiber systems. Therefore, directly fabricating optical thin film structures with spectral modulation, thermal management, and environmental protection functions on fiber substrates is a more promising solution that aligns with the development direction of all-fiber integration.
[0005] Against this backdrop, directly integrating the reflection / transmission function of the resonant cavity into the fiber substrate and constructing an equivalent cavity mirror through end-face optical thin films is an important technical approach for the all-fiber transformation of mid-infrared fiber lasers. This approach can eliminate free-space coupling links, reduce system tuning difficulty, and reduce intracavity loss through precise spectral design, thus suppressing thermal effects at the source. While traditional mid-infrared high-refractive-index materials (such as Ge and Si) have good infrared transmittance in the 2–5 μm range, their transmittance is limited in the 800–1000 nm range. Significant intrinsic interband absorption exists in the near-infrared pump band, resulting in insufficient near-infrared pump light transmittance, which cannot meet the high coupling efficiency requirements. This makes it impossible for mid-infrared resonator structures designed based on such materials to simultaneously meet the dual requirements of high pump light coupling efficiency and high laser band reflectivity. Meanwhile, although sulfide and fluoride materials have excellent mid-infrared optical properties, they generally suffer from low mechanical strength, poor thermal stability, and insufficient adhesion. Under high-power operating conditions, they are prone to thermal damage or film failure. It is evident that existing conventional mid-infrared thin film materials are difficult to simultaneously meet the comprehensive requirements of all-fiber lasers for pump band transmittance, laser band reflection, and high power stability.
[0006] Furthermore, most existing mid-infrared thin-film technologies are designed only for a single wavelength band, failing to achieve a synergistic match between low absorption in the near-infrared band and high reflectivity in the mid-infrared band. For example, Chinese invention publication CN107290814B proposes an all-dielectric dichroic element for visible light, laser, and mid-infrared bands, using ZnSe / Ge and ZnS / YbF3 as high and low refractive index media pairs. Through a multilayer film interference structure, it achieves high transmission in the 3.0–5.0 μm mid-infrared band and high reflectivity in the 0.6–0.9 μm visible light band. However, its design target is only for the visible and mid-infrared bands, without optimizing for low absorption in the 900–1500 nm near-infrared pump band. Materials such as Ge and ZnSe exhibit significant intrinsic absorption in this band, which can easily lead to severe heat accumulation when directly applied to fiber optic substrate cavity mirrors. The Chinese invention with publication number CN120195781A addresses the problems of chalcogenide glass fiber substrates being prone to deliquescence and having high reflection loss by designing a Sub / M / B / C / A multilayer composite thin film structure. By adding a blocking layer and an antireflection layer, it achieves broadband antireflection in the mid-infrared band and end-face moisture barrier protection. However, the film materials used in this scheme are still mainly Ge, ZnS and chalcogenide compounds, which do not solve the inherent absorption loss problem in the near-infrared pump band. Under high-power pumping conditions, the thermal effect is prominent and cannot meet the requirements for long-term stable operation of all-fiber lasers. To reduce optical absorption and improve the laser damage threshold of thin films, some studies have attempted to construct film structures using a single oxide system. For example, Chinese invention patent CN120505592A proposes a method for preparing porous all-SiO2 laser reflective films. This method involves alternating deposition of SiO2 and SiO2-Al2O3 mixed films followed by acid etching to form a dense all-silica film system alternating between dense and porous SiO2. This achieves extremely low optical absorption and a high laser damage threshold in the ultraviolet to near-infrared bands. However, this patent focuses on ultraviolet laser reflective films in the 355 nm band. The application scenarios and film system design are geared towards the requirements of short wavelengths and high damage thresholds. It does not address the dual-band synergistic optimization of the 2–5 μm mid-infrared laser band and the 900–1500 nm near-infrared pump band, nor does it incorporate the fiber optic substrate cavity mirror structure for adaptation design. Therefore, it cannot directly solve the core problem of matching the absorption in the pump band and the reflection in the working band of the end-face cavity mirror of the mid-infrared all-fiber laser.
[0007] It is particularly noteworthy that existing publicly disclosed multilayer film structures (such as typical M / HLHL / M type metal-dielectric alternating structures) are mainly used in structural color displays, laser protection, stealth coatings, or free-space optical mirrors. These solutions generally incorporate a metal layer to achieve strong absorption or high reflectivity. However, metallic materials cannot achieve high transmittance across a wide spectral range from near-infrared to mid-infrared, exhibiting intrinsic absorption and high scattering losses. Therefore, they are ill-suited to the core requirement of this invention: low-loss transmission across the entire spectrum.
[0008] More importantly, none of the aforementioned existing technologies are designed for the end face of the fiber laser resonator. Their structures and functions are only optimized for free-space optical paths, and they do not involve the core technical points of this invention, such as fiber substrate integration, fiber substrate moisture resistance, precise stress matching at the film-substrate interface, and coordinated control of pump / laser dual-band (or multi-band) modes. Therefore, existing multilayer film structures cannot be directly applied to the end face integration scenario of the mid-infrared all-fiber laser of this invention, nor can they solve the key technical challenges faced by this invention, such as thermal effects, environmental stability, and high-power operation.
[0009] Therefore, there is an urgent need to develop an end-face thin-film solution suitable for 3-5μm mid-infrared all-fiber lasers. The key lies in selecting and employing a core material system that combines low near-infrared absorption, high mid-infrared reflectivity, high resistance to laser damage, and strong environmental stability. Through precise design of the film structure and synergistic optimization of process parameters, the solution can achieve the dual spectral requirements of high transmittance in the near-infrared pump band and high reflectivity in the 3-5μm mid-infrared laser band, while also possessing excellent resistance to laser damage, reliable moisture resistance, and stable resistance to environmental disturbances. This solution will break through existing technological bottlenecks from two dimensions: fundamental material innovation and structural integration optimization, providing a new technological path for the high integration, miniaturization, and long-term reliable operation of mid-infrared fiber lasers. Summary of the Invention
[0010] In view of this, the purpose of this invention is to propose a 3-5μm mid-infrared all-fiber laser all-oxide thin film. By depositing a multilayer oxide thin film structure with specific spectral response and stress distribution characteristics on the fiber substrate of the mid-infrared all-fiber laser, the end-face thin film can simultaneously serve as an equivalent reflector of the laser resonator, an end-face protective layer, an adhesive layer, and a stress buffer layer without introducing a free space optical path, thereby realizing the end-face integrated construction of the mid-infrared fiber laser resonator.
[0011] To achieve the above-mentioned technical objectives, the technical solution adopted by this invention is as follows: This invention provides a 3-5μm mid-infrared all-fiber laser all-oxide film, wherein the all-oxide film is disposed on an optical fiber substrate and comprises, in sequence from the direction closest to the optical fiber substrate to the direction furthest from the optical fiber substrate: an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M. The adhesive layer A is disposed on the optical fiber substrate to enhance the interfacial bonding stability between the film layer and the optical fiber substrate. The gradient stress buffer layer G is disposed on the surface of the adhesive layer A, and its refractive index increases gradually from the inside to the outside. It is used to achieve a smooth transition of optical and physical parameters to release residual stress at the interface. The core reflective layer R is disposed on the surface of the gradient stress buffer layer G and adopts a periodic structure of alternating stacks of high refractive index oxide layers and low refractive index oxide layers to achieve high transmission in the near-infrared pump band and reflection in the mid-infrared laser band. The damage-resistant layer L is disposed on the surface of the core reflective layer R and adopts an asymmetric single-period or double-period structure consisting of a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer. It is used to confine the laser electric field peak within the low-absorption medium layer to improve the laser damage resistance. The moisture-proof protective layer M is disposed on the surface of the damage-resistant layer L, forming the outermost protective barrier to block moisture and pollutants.
[0012] Furthermore, the adhesive layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer oxide composite structure; The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and has a physical thickness of 20-50nm. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide with a physical thickness of 20-50 nm. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5. The multilayer oxide composite structure consists of multiple layers of mixed SiO2 and metal oxide with different component ratios arranged sequentially, with a total physical thickness of 20-50 nm.
[0013] Furthermore, the gradient stress buffer layer G adopts a three-layer stepped gradient composite structure with a total physical thickness of 120-270nm, consisting of the following layers from the inside out: A low-refractive-index hybrid layer has a refractive index of 1.50-1.70 and a physical thickness of 50-120 nm; the low-refractive-index hybrid layer is an aluminum-rich Al2O3-SiO2 hybrid layer or a yttrium-rich Y2O3-SiO2 hybrid layer, wherein the Al2O3 or Y2O3 content is 55-80 mol%, and the SiO2 content is 20-45 mol%. A medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90 and a physical thickness of 50-100 nm; the medium-refractive-index pure oxide layer is made of Al2O3, Y2O3, or HfO2; and A high refractive index matching layer, with a refractive index of 1.90-2.30 and a physical thickness of 20-50 nm, is used to achieve refractive index matching with the high refractive index oxide layer of the core reflective layer R; the high refractive index matching layer adopts HfO2, ZrO2, Ta2O5 or TiO2.
[0014] Furthermore, the core reflective layer R has a total of 3–13 layers and a total thickness of 0.7–11.2 μm. It is arranged in a symmetrical or approximately symmetrical manner with a high-refractive-index oxide layer or a low-refractive-index oxide layer at the center and a high-refractive-index oxide layer as the outermost layer. Specifically, the symmetrical arrangement means that the high-refractive-index oxide layer and the low-refractive-index oxide layer have a symmetrical structure and use identical materials at symmetrical positions; the approximately symmetrical arrangement means that the high-refractive-index oxide layer and the low-refractive-index oxide layer have a symmetrical structure and use different materials at symmetrical positions. The high-refractive-index oxide layer is made of at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2, and Nb2O5, with a refractive index of 1.90–2.35 and a single-layer physical thickness of 200–700 nm; wherein the molar doping ratio of Ti in the TiTa2O5 is 5%–20%; The low-refractive-index oxide layer is made of at least one of SiO2, Al2O3, MgO and Y2O3, with a refractive index of 1.39–1.77 and a single-layer physical thickness of 300–1000 nm.
[0015] Furthermore, the single-period structure in the damage-resistant layer L, from the inside out, includes: A low-refractive-index electric field isolation layer with a physical thickness of 850–900 nm is used; the low-refractive-index electric field isolation layer is made of SiO2. A high-refractive-index transition layer with a physical thickness of 25–65 nm; the high-refractive-index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5; A low-refractive-index surface strengthening layer with a physical thickness of 290–370 nm; the low-refractive-index surface strengthening layer is made of Y2O3, Al2O3 or MgO; The total physical thickness of the single-period structure is controlled at 1165–1335 nm; The physical thickness of the high-refractive-index transition layer accounts for 1.93%–5.4% of the total thickness of the damage-resistant layer in a single cycle, and the total thickness of the low-refractive-index electric field isolation layer and the low-refractive-index surface strengthening layer accounts for more than 94% of the total thickness of the damage-resistant layer in a single cycle.
[0016] The dual-period structure of the damage-resistant layer L is composed of two sets of single-period structures superimposed on each other.
[0017] Furthermore, the moisture-proof protective layer M adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure; The monolayer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and the physical thickness of the monolayer is 100–130 nm. The monolayer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5, and the physical thickness of the monolayer is 100–130 nm. The multilayer gradient composite structure is a mixed layer of SiO2 and metal oxide with different component ratios arranged in multiple layers, with a single layer physical thickness of 30–80 nm; or a pure oxide structure arranged in multiple layers, each pure oxide structure using Al2O3, HfO2 or Y2O3, with a single layer physical thickness of 30–50 nm. In the bilayer silicon-aluminum gradient hybrid structure, the thickness of each single layer is 30–80 nm, and the overall thickness is controlled between 60–160 nm. In the trilayer Al2O3 / HfO2 / Al2O3 composite structure, the thickness of each layer is 30–50 nm, and the overall physical thickness of the moisture-proof protective layer is controlled between 90–150 nm.
[0018] Furthermore, the all-oxide thin film is used as an input reflector or output coupler for the resonant cavity of a mid-infrared all-fiber laser; when used as an input reflector, the core reflective layer R has a reflectivity of 95%-99.5% for the 3600-4000nm wavelength band; when used as an output coupler, the core reflective layer R has a reflectivity of 60%-85% for the 3600-4000nm wavelength band.
[0019] This invention also provides a method for preparing a 3-5 μm mid-infrared all-fiber laser all-oxide thin film, which includes the following steps: Step 1: After cleaning and pre-treating the fiber substrate, fix the fiber substrate in the fixture and smoothly install it into the vacuum coating cavity, so that the fiber substrate is perpendicular to the direction of the film evaporation beam. Step 2: Evacuate the vacuum coating chamber to a preset vacuum level and pre-melt various oxide film materials respectively. The oxide film materials include materials for forming the bonding layer A, gradient stress buffer layer G, core reflective layer R, damage-resistant layer L and moisture-proof protective layer M. Step 3: According to the preset all-oxide thin film structure, the bonding layer A, the gradient stress buffer layer G, the core reflective layer R, the damage resistance layer L and the moisture-proof protective layer M are deposited layer by layer from the inside to the outside on the optical fiber substrate to obtain a sample. During the deposition process, a segmented temperature control strategy is adopted to control the temperature of the optical fiber substrate. Step 4: After all film layers have been deposited, the sample is subjected to in-situ vacuum annealing under vacuum conditions to release residual stress inside the film layers. Step 5: After annealing, allow the sample to cool naturally to room temperature, break the vacuum, and remove the coated sample. This sample is the all-oxide film.
[0020] Furthermore, in step 1, the optical fiber substrate is a quartz optical fiber or a fluoride optical fiber; in step 2, the preset vacuum level is 8 × 10⁻⁶. -3 Pa; The pre-melting treatment adopts a gradient heating method to fully release adsorbed water vapor and residual gas inside the film material; The segmented temperature control strategy in step 3 is as follows: when the temperature of the optical fiber substrate rises to the preset first temperature threshold, deposition is paused, and the substrate is cooled to below the preset second temperature threshold under continuous vacuum conditions, and then deposition is resumed. This cycle is repeated until all film layers are deposited, wherein the second temperature threshold is less than the first temperature threshold; The in-situ vacuum annealing temperature in step 4 is 200-400℃, the holding time is 1-3 hours, and the vacuum degree is maintained at 1×10 -3 Below Pa; after annealing, allow the sample to cool naturally to room temperature with the chamber at a cooling rate not exceeding 2℃ / min.
[0021] Furthermore, in step 3, a combination of electron beam evaporation and ion-assisted deposition is used for deposition, and the deposition process is as follows: (1) When the bonding layer A is deposited, the deposition rate is 0.1-0.3 nm / s, the temperature of the optical fiber substrate is controlled at 80-120℃, and the bonding layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure or a multi-layer oxide composite structure. a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and the deposition thickness is 20-50nm; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, with a deposition thickness of 20-50 nm. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5. c. The multilayer oxide composite structure adopts a multilayer mixture of SiO2 and metal oxide with different component ratios. The molar ratio of SiO2 to metal oxide is controlled by controlling the electron beam evaporation rate. The total deposition thickness is 20-50 nm. (2) When depositing the gradient stress buffer layer G, three stepped gradient composite structures are deposited sequentially: The first layer is a low-refractive-index mixed layer with a refractive index of 1.50-1.70, a deposition thickness of 50-120 nm, and a deposition rate of 0.1-0.3 nm / s. This low-refractive-index mixed layer is either an aluminum-rich Al₂O₃-SiO₂ mixed layer or a yttrium-rich Y₂O₃-SiO₂ mixed layer, wherein the Al₂O₃ or Y₂O₃ content is 55-80 mol%, and the SiO₂ content is 20-45 mol%. The second layer is a medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90, a deposition thickness of 50-100 nm, and a deposition rate of 0.1-0.2 nm / s; the medium-refractive-index pure oxide layer is made of Al2O3, Y2O3, or HfO2. The third layer is a high refractive index matching layer with a refractive index of 1.90-2.30, a deposition thickness of 20-50 nm, and a deposition rate of 0.05-0.15 nm / s; the high refractive index matching layer is made of HfO2, ZrO2, Ta2O5, or TiO2. During the deposition of the three-layer stepped gradient composite structure, the ion source-assisted energy was 500-800 eV, and the ion beam current density was 50-100 μA / cm². 2 ; (3) When depositing the core reflective layer R, a method of alternating stacking of high-refractive-index oxide layers and low-refractive-index oxide layers is adopted. The high-refractive-index oxide layers are at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2, and Nb2O5, with a refractive index of 1.90-2.35, a single-layer deposition thickness of 200-700 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source assisted energy of 600-1000 eV. Among them, when depositing TiTa2O5, Ti-doped Ta2O5 is used, and the molar ratio of Ti doping is controlled to be 5%-20%. The low-refractive-index oxide layers are at least one of SiO2, Al2O3, MgO, and Y2O3, with a refractive index of 1.39-1.77, and a single-layer deposition thickness of 300-1000 nm. The deposition rate is 0.2-0.4 nm / s, and the ion source assisted energy is 300-500 eV. The thickness of each layer is optimized according to the preset mid-infrared standing wave field distribution. The total number of layers is 3-13, and the total thickness is 0.7-11.2 μm. (4) When depositing the damage-resistant layer L, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric single-period structure, or a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, a low-refractive-index surface passivation layer, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric double-period structure: The low-refractive-index electric field isolation layer is made of SiO2, with a deposition thickness of 850-900 nm, a deposition rate of 0.2-0.4 nm / s, and an ion source-assisted energy of 300-500 eV. The high refractive index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5, with a deposition thickness of 25-65 nm, a deposition rate of 0.05-0.15 nm / s, and an ion source assisted energy of 500-800 eV. The low-refractive-index surface passivation layer is made of Y2O3, Al2O3 or MgO, with a deposition thickness of 290-370 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source-assisted energy of 500-800 eV. During the deposition process, the temperature of the optical fiber substrate is controlled to not exceed 120℃; (5) When depositing the moisture-proof protective layer M, a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure is adopted; a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3; the deposition thickness is 100-130nm, the deposition rate is 0.1-0.2nm / s, and the ion source assisted energy is 500-800eV; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5, and the deposition thickness is 100–130 nm. c. The multilayer gradient composite structure is a mixture of SiO2 and metal oxides with different component ratios arranged in multiple layers, with a single layer deposition thickness of 30–80 nm; or a multilayer pure oxide structure, with each pure oxide structure using Al2O3, HfO2 or Y2O3, and a single layer deposition thickness of 30–50 nm.
[0022] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art: 1. A five-layer functional hierarchical integrated architecture enables integrated multi-functional collaboration of the end face, supporting the integration of all-fiber resonant cavities: This invention integrates four functional zones—dual-band spectral modulation, gradient stress mitigation, high-power damage resistance, and long-term moisture and corrosion protection—into an optical fiber substrate, forming a layered, multi-layered, and synergistic all-oxide integrated film system architecture, which differs from the traditional single-function film system design. Addressing the challenges of high spectral modulation requirements, concentrated thermal loads, film-substrate stress mismatch, and fiber substrate deliquescence at the end face of 3–5 μm mid-infrared all-fiber lasers, a five-layer progressive composite film system is designed: an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M. Through the division of labor and step-by-step matching of each functional layer, multiple functions—high pump light transmittance, mid-infrared laser resonant feedback, interface stress mitigation, laser damage protection, and environmental moisture protection—are integrated into the optical fiber substrate. This structure can replace traditional bulk cavity mirrors, fiber end caps, and free-space coupling elements, which helps to realize the full fiber resonant cavity integration of mid-infrared lasers, improve system integration, simplify assembly and adjustment processes, and reduce vibration interference and optical path drift problems introduced by discrete optical components, thereby improving the operating stability of lasers under complex conditions.
[0023] 2. Ti-doped Ta2O5 functional materials improve mid-infrared thin film spectroscopy and damage resistance: This invention selects Ti-doped Ta₂O₅ (TiTa₂O₅) as the main high-refractive-index material for the core reflective layer R. Utilizing the defect modulation mechanism of Ti, a performance balance of high refractive index, low pump absorption, and a high laser damage threshold is achieved in the 4μm mid-infrared band. Compared to traditional single oxides, this material system helps achieve synergistic effects within the film system: maintaining the required high refractive index to meet the interference reflection requirements in the mid-infrared band while reducing absorption in the near-infrared pump band, thereby achieving high transmittance in the 888nm and 1645nm pump bands, and simultaneously achieving spectral modulation of high reflectance or controllable partial reflectance in the 3600–4000nm operating band. This material selection can mitigate the end-face heat accumulation and thermal distortion problems caused by pump light absorption at the material level, improve pump coupling efficiency, suppress the accumulation of thermal effects under high-power lasers, and provide support for the stable operation of mid-infrared all-fiber lasers.
[0024] 3. Gradient stress buffer system to mitigate the risk of membrane substrate detachment and membrane cracking: This invention employs a two-layer transition system consisting of an adhesive layer A and a gradient stress buffer layer G to address the shortcomings of traditional single-layer transition layers, such as abrupt property changes and stress concentration. Adhesive layer A enhances the interfacial bonding strength between the film and substrate through a silicon-aluminum composite bonding mechanism and repairs microscopic defects in the fiber substrate. The gradient stress buffer layer G utilizes a three-layer stepped composition gradient design, ensuring a smooth and continuous transition in refractive index, coefficient of thermal expansion, and mechanical modulus. This gradually releases the residual interfacial stress generated by the stacking of multiple film systems, reducing it by more than 40% under experimental conditions. Simultaneously, the stepped nucleation environment helps induce a uniform and dense growth structure in the upper core reflective layer R, suppressing the formation of defects such as nodules and large grains, thereby improving the structural stability and optical consistency of the film system.
[0025] 4. A dual-layer external protective structure that combines damage resistance and moisture protection, taking into account both laser tolerance and environmental protection: This invention employs a layered design for laser damage resistance and environmental moisture protection, clearly defining functional boundaries and avoiding the shortcomings of mixed functions in traditional composite protective layers. The inner damage resistance layer L utilizes a pure HfO2 / ZrO2+Y2O3 dielectric system and an asymmetric optical field modulation structure. Through electric field peak isolation, the high-energy laser field is confined within a low-absorption, high-damage-resistance dielectric layer, reducing the risk of thermal damage from the perspective of optical field distribution and improving the laser damage threshold of the film system. The outer moisture-proof protective layer M is primarily composed of a dense silicon-aluminum gradient oxide structure, forming a dense protective barrier that effectively blocks the intrusion of moisture, corrosive media, and dust contaminants, mitigating the problem of hygroscopicity in fluoride fiber substrates. This structure achieves environmental protection of the fiber substrate without the need for additional end caps or complex encapsulation, contributing to improved long-term reliability of lasers under harsh conditions such as high and low temperatures and high humidity. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a schematic diagram of the structure of a 3-5μm mid-infrared all-fiber laser all-oxide thin film according to the present invention.
[0028] Figure 2 This is a schematic diagram of the structure of a 3.9μm all-fiber laser, which is constructed with a five-element optical thin film composed of TiTa2O5 as an aid.
[0029] Figure 3The image shows the reflection spectrum of a pentagonal optical fiber end-face dichroic laser reflective film composed of TiTa2O5 in the 0.8µm-4µm wavelength range, as described in Example 1.
[0030] Figure 4 The image shows the reflection spectrum of a five-element optical fiber end-face dichroic laser reflective film composed of TiTa2O5 in the 0.8µm-4µm wavelength range, as described in Example 2.
[0031] Figure 5 The image shows the reflection spectrum of a fiber end-face dichroic laser reflective film composed only of TiTa2O5 and SiO2 in the 0.8µm-4µm wavelength range, as described in Example 3.
[0032] Figure 6 The image shows the reflection spectrum of a high refractive index gradient all-dielectric fiber end-face dichroic laser reflective film in the 0.8 μm-4 μm band in Example 4.
[0033] Figure 7 Example 5 shows the reflection spectrum of a 3.9 μm laser output film composed of TiTa2O5 in the 0.8 μm-4 μm wavelength range. Detailed Implementation
[0034] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be particularly noted that the following embodiments are for illustrative purposes only and do not limit the scope of the invention. Similarly, the following embodiments are only some, not all, embodiments of the present invention, and all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] This invention achieves innovative breakthroughs in film architecture and functional integration, proposing the AGRLM pentagonal composite film system, composed of an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M. It integrates five core functions into the fiber substrate: high-strength film-substrate bonding, interface stress mitigation, multi-band spectral modulation, laser damage protection, and environmental moisture protection. This achieves synergistic spectral modulation of high transmittance in the near-infrared pump band and high / controllable partial reflection in the 3–5μm mid-infrared laser band. Simultaneously, it endows the film with low absorption, low temperature rise, and high resistance to laser damage, and significantly improves the moisture resistance and long-term structural stability of the fluoride fiber substrate. Through Ti-doped Ta₂O₅ material, a synergistic design of TiTa₂O₅ and the AGRLM pentagonal architecture is achieved. This invention effectively solves the technical challenges of simultaneously achieving spectral matching, thermal management, mechanical stability, and environmental tolerance in existing technologies. It provides a highly integrated, highly reliable, and engineerable end-face thin-film solution for mid-infrared all-fiber lasers, which can directly replace traditional discrete resonant cavity devices, significantly simplifying the system structure and improving operational stability.
[0036] This invention discloses a 3-5 μm mid-infrared all-oxide thin film for a mid-infrared all-fiber laser. Utilizing an all-oxide material system, compared to traditional metal-containing or chalcogenide / fluoride films, the all-oxide system exhibits lower intrinsic absorption, superior thermal stability, and better mechanical strength in the near-infrared to mid-infrared bands. It also enables low-loss transmission of near-infrared pump light and mid-infrared laser light, fundamentally suppressing thermal effects. Through spectral design of the multilayer dielectric film, the film achieves high transmittance in the near-infrared pump band (e.g., 888 nm and 1.6 μm) to ensure efficient coupling of the pump light into the gain fiber. Simultaneously, high reflectivity is achieved in the mid-infrared laser operating band near 4 μm (preferably 3600–4000 nm), thereby forming stable laser resonator feedback conditions on the fiber substrate. By reducing the absorption loss at the end face in the near-infrared pump band, the localized temperature rise and thermal lensing effect caused by end face absorption can be effectively suppressed, improving the output stability of the laser under high-power operating conditions.
[0037] Please see Figures 1-2 This invention discloses a 3-5μm mid-infrared all-fiber laser all-oxide thin film. The all-oxide thin film is disposed on an optical fiber substrate, realizing the integration of resonant cavity, precise spectral control, gradient stress buffering, and long-term environmental protection. The all-oxide thin film is an all-oxide, low-absorption, low-stress multilayer composite film system, which includes, from the direction closest to the optical fiber substrate to the direction furthest from the optical fiber substrate, an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M. Each functional layer cooperates and coordinates in stress control, optical function, laser tolerance, and environmental protection to jointly ensure the overall performance and long-term operational reliability of the film system. (1) Adhesion Layer A The adhesive layer A is disposed on the optical fiber substrate to enhance the interfacial bonding stability between the film layer and the optical fiber substrate, and to provide a uniform and reliable growth interface for subsequent functional films. In this embodiment, the adhesive layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer oxide composite structure; The single-layer pure oxide structure uses Al2O3, HfO2 or Y2O3, with a physical thickness of 20-50 nm. Al2O3 has good interfacial adhesion, chemical stability and environmental stability, which can enhance the bonding ability between the film layer and the optical fiber substrate, and play an interfacial passivation role on the surface of the optical fiber substrate.
[0038] The monolayer mixed oxide structure employs a mixed layer of SiO2 and metal oxides with a physical thickness of 20-50 nm, more preferably 30 nm. This mixed layer introduces a metal-oxygen network and a silicon-oxygen network to synergistically construct a composite bonding structure, enhancing the interfacial bonding ability while ensuring film density. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5, and Nb2O5; preferably, an Al2O3-SiO2, ZrO2-SiO2, HfO2-SiO2, or Y2O3-SiO2 mixed oxide system is used to obtain better interfacial bonding performance and process stability, with the Al2O3-SiO2 mixed oxide system being the most preferred. Specifically, the SiO2 content in the Al2O3-SiO2 monolayer mixed oxide structure is 60–85 mol%, and the Al2O3 content is 15–40 mol%, more preferably (SiO2). 0.65 (Al2O3) 0.35 Mixed oxides, with a total thickness controlled between 20 and 50 nm, and an optimal value of 30 nm; The multilayer oxide composite structure comprises multiple layers of mixed SiO2 and metal oxides with different component ratios, arranged sequentially, with a total physical thickness of 20-50 nm. Silicon-rich (SiO2) is preferred. 0.65 (Al2O3) 0.35 Mixed layer and equimolar ratio (SiO2) 0.50 (Al2O3) 0.50 The hybrid layer forms a bilayer structure, with each single layer having a thickness of 10–25 nm and the overall thickness maintained at 20–50 nm, preferably with a total thickness of 30 nm.
[0039] When using a SiO2-metal oxide hybrid system, a stable interfacial transition layer can be formed between the optical fiber substrate and the upper oxide film system, improving the bonding stability between the film layer and the optical fiber substrate. The silicon-rich hybrid oxide exhibits good chemical compatibility and property matching characteristics with the quartz optical fiber substrate, which is beneficial for enhancing interfacial adhesion and improving film growth quality. Simultaneously, the hybrid oxide structure can cover and modify microscopic defects on the surface of the optical fiber substrate, reducing the interfacial defect density and promoting the uniform and continuous growth of subsequent film layers, thereby improving the adhesion reliability and long-term stability of the entire film system.
[0040] Through the above design, the adhesive layer A can improve the bonding stability of the membrane-substrate interface, alleviate the interfacial stress mismatch, improve the deposition quality and structural reliability of subsequent membrane layers, and provide support for the long-term stable operation of the entire end-face thin film structure.
[0041] (2) Gradient-Index Stress Buffer Layer G The gradient stress buffer layer G is disposed on the surface of the adhesive layer A, and its refractive index increases gradually from the inside to the outside. It is used to achieve a smooth transition of optical and physical parameters to release residual stress at the interface. In this embodiment, the gradient stress buffer layer G adopts a three-layer stepped gradient composite structure with the refractive index gradually increasing from the inside to the outside, and the total physical thickness is 120-270 nm, preferably 180 nm, and the layers from the inside to the outside are as follows: A low-refractive-index hybrid layer has a refractive index of 1.50-1.70 and a physical thickness of 50-120 nm, preferably 80 nm; the low-refractive-index hybrid layer is an aluminum-rich Al2O3-SiO2 hybrid layer or a yttrium-rich Y2O3-SiO2 hybrid layer, wherein the Al2O3 or Y2O3 content is 55-80 mol%, and the SiO2 content is 20-45 mol%. A medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90 and a physical thickness of 50-100 nm; the medium-refractive-index pure oxide layer is made of Al2O3, Y2O3, or HfO2; and A high refractive index matching layer, with a refractive index of 1.90-2.30 and a physical thickness of 20-50 nm, is used to achieve refractive index matching with the high refractive index oxide layer (1.90-2.35) of the core reflective layer R; the high refractive index matching layer adopts HfO2, ZrO2, Ta2O5 or TiO2.
[0042] Through a stepwise increasing design of composition and refractive index, this layer can achieve a continuous and smooth transition of refractive index, coefficient of thermal expansion and mechanical modulus, completely eliminate abrupt changes in interface properties, gradually release the residual stress at the interface generated by the stacking of multilayer films, inhibit defect growth and nodule formation, and significantly improve the overall structural stability of the film system.
[0043] This structure achieves a smooth transition in refractive index, coefficient of thermal expansion, and mechanical modulus through a three-layer material stepwise composition and property matching, thoroughly improving the interface abruptness problem in multilayer film systems. The aluminum-rich hybrid layer forms a stable Si–O–Al bridge bond with the silicon-rich component of the binder layer A, smoothly transitioning the silicon-oxygen and aluminum-oxygen network structures and avoiding abrupt interface property changes. The dense Al2O3 layer in the middle acts as a rigid support medium, effectively improving the overall density and mechanical strength of the film. The refractive index of the outer HfO2 transition layer is highly matched with the high-refractive-index TiTa2O5 material of the core reflective layer R, completely eliminating the property abrupt difference between high and low refractive index interfaces. Compared to traditional single homogeneous transition films, this three-layer gradient structure can reduce the residual stress at the interface by more than 40%, effectively avoiding the risk of film cracking and delamination caused by stress concentration. Simultaneously, the stepwise nucleation environment induces the core reflective layer to generate a uniform and dense columnar crystal structure, inhibiting large grain growth and nodule defects, significantly improving the overall structural stability and optical uniformity of the film system.
[0044] (3) Core reflective layer R (Reflective Layer) The core reflective layer R is disposed on the surface of the gradient stress buffer layer G and adopts a periodic structure of alternating stacks of high refractive index oxide layers and low refractive index oxide layers to achieve high transmission in the near-infrared pump band and reflection in the mid-infrared laser band. In this embodiment, the core reflective layer R is flexibly designed as a binary, ternary, or gradient high refractive index structure according to spectral requirements, with a total of 3–13 layers and a total thickness of 0.7–11.2 μm. The overall structure is symmetrically or approximately symmetrically arranged with a high refractive index oxide layer or a low refractive index oxide layer as the center and a high refractive index oxide layer as the outermost layer. Specifically, the symmetrical arrangement means that the high refractive index oxide layer and the low refractive index oxide layer have a symmetrical structure and use identical materials at symmetrical positions; the approximately symmetrical arrangement means that the high refractive index oxide layer and the low refractive index oxide layer have a symmetrical structure and use different materials at symmetrical positions. The high-refractive-index oxide layer is made of at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2 and Nb2O5, with a refractive index of 1.90-2.35 and a single-layer physical thickness of 200-700 nm; wherein, the molar ratio of Ti doping in TiTa2O5 is 5%-20%, preferably 10%-15%, and it has low intrinsic absorption in the mid-infrared, high thermal stability and excellent laser resistance characteristics; By introducing Ti into the Ta2O5 matrix, the band structure, defect state density, and local polarization characteristics of the material can be tuned. The broad-band absorption loss of Ta2O5 films essentially stems from its internal defects, specifically in two aspects: First, defects increase the width of the Urbach band tail, which quantitatively reflects the positive correlation between the film's structural disorder and absorption loss; second, oxygen vacancies form three defect energy levels of 1.5 eV, 0.5 eV, and 0.2 eV in the band gap. Low-energy lasers are easily captured by these levels, leading to additional absorption loss. The Urbach band tail model can accurately quantify absorption loss, and the defect energy level concept can clearly and qualitatively explain the absorption mechanism. Together, they reveal the core principle that "defects dominate Ta2O5 absorption." The reason why Ti-doped Ta2O5 can significantly reduce absorption lies in the targeted suppression of these defects. Previous studies have confirmed that the incorporation of TiO2 can effectively eliminate shallow-level defects in the bandgap of Ta2O5. This mechanism also applies to Ti-doped modification: the introduction of Ti can fill oxygen vacancies in Ta2O5, reduce the number of defect levels, and simultaneously reduce the disorder of the film structure and narrow the Urbach band tail, thereby weakening the two absorption pathways mentioned above at their source. This allows the resulting film to maintain a high refractive index while effectively reducing absorption loss in the 3–5 μm mid-infrared band. The above mechanism is used to explain the possible physical reasons for the reduced absorption loss in the material system of this invention, but the technical effects of this invention are not limited to the above mechanistic explanation.
[0045] The preferred molar ratio of Ti doping is 5%–20%, more preferably 10%–15%. Appropriate Ti doping helps suppress oxygen vacancy defects in Ta₂O₅ films, improves the stability of the amorphous structure, reduces absorption loss in the mid-infrared band, and increases film density and laser damage threshold. When the Ti doping amount is too low, the above-mentioned improvement effects are not significant; when the Ti doping amount is too high, it may lead to a decrease in local structural uniformity, increased crystallization tendency, and increased scattering loss, thus hindering further improvement in the film's optical and laser damage performance. Therefore, compared to single Ta₂O₅, TiTa₂O₅ has a higher effective refractive index, making it more suitable for constructing high-reflectance or high-contrast multilayer films in the mid-infrared band; compared to single TiO₂, TiTa₂O₅ exhibits significantly reduced absorption in the mid-infrared band while maintaining a high laser damage threshold and good structural stability.
[0046] In summary, TiTa2O5 combines the high refractive index of TiO2 with the low absorption and high laser damage resistance of Ta2O5, effectively solving the long-standing challenge of balancing performance in the selection of mid-infrared end-face thin film materials. It is an ideal novel oxide material for mid-infrared fiber laser end-face thin films. The selection of Ti-doped Ta2O5 in this invention is not a conventional choice or simple replacement in the field, but rather a mechanistic innovation addressing the long-standing technical bottleneck of the inability to simultaneously achieve low absorption, high refractive index, and high damage resistance in the 3-5μm wavelength band.
[0047] The low-refractive-index oxide layer is made of at least one of SiO2, Al2O3, MgO and Y2O3, with a refractive index of 1.39–1.77 and a single-layer physical thickness of 300–1000 nm. It has excellent optical uniformity, high density and good interfacial compatibility. The single-layer physical thickness of the high-refractive-index oxide layer is 200–700 nm, and the single-layer physical thickness of the low-refractive-index oxide layer is 300–1000 nm. The thickness of each layer is precisely optimized based on the mid-infrared standing wave field distribution rather than using a uniform λ / 4 design. Relying on the multilayer thin film interference effect, it is possible to achieve coordinated control of high transmission in the near-infrared pump band and high reflection or preset partial reflection in the mid-infrared laser band. At the same time, it also has low optical absorption, low thermal stress and excellent laser tolerance.
[0048] This layer can be flexibly designed as a binary TiTa₂O₅ / SiO₂ structure, a pentagonal TiTa₂O₅-TiO₂ / SiO₂ composite structure, or a Ta₂O₅-TiTa₂O₅-TiO₂ gradient high-refractive-index structure according to spectral requirements. The total number of layers can be adjusted from 3 to 13 layers according to the target reflectivity, and the overall arrangement is symmetrical or approximately symmetrical. By adjusting the stacking period and the ratio of high-refractive-index materials, a wide range of reflectivity of 60%–99.5% can be achieved in the 3600–4000 nm wavelength band, which can be adapted to the needs of different devices such as high-reflectivity input mirrors and partially reflective output mirrors.
[0049] Based on the characteristics of the laser standing wave field distribution, this layer preferentially uses highly stable, low-loss TiTa2O5 material in the high-field-strength region, while TiO2 and Ta2O5 materials can be introduced in the low-field-strength region to optimize overall thermal and structural stress while ensuring spectral performance. This layer can achieve a dual-spectral modulation effect of high transmission in the near-infrared 888 nm and 1645 nm pump bands and high reflection or preset partial reflection in the mid-infrared working band of 3600–4000 nm, providing stable laser resonance feedback for the fiber resonator and ensuring stable laser start-up and efficient output.
[0050] (4) Laser-Resistant Layer (L) The anti-damage layer L is disposed on the surface of the core reflective layer R. It adopts an asymmetric single-period or double-period structure consisting of a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer. This structure is used to confine the laser electric field peak within the low-absorption medium layer to improve the resistance to laser damage. The main design goals of this layer are laser damage suppression and light field redistribution. Under the premise of minimal impact on the overall reflective performance of the film system, it achieves a significant improvement in the film's resistance to laser damage.
[0051] In this embodiment, the single-cycle structure in the damage-resistant layer L, from the inside out, includes: A low-refractive-index electric field isolation layer with a physical thickness of 850–900 nm is used; the low-refractive-index electric field isolation layer is made of SiO2. A high-refractive-index transition layer with a physical thickness of 25–65 nm; the high-refractive-index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5; A low-refractive-index surface strengthening layer with a physical thickness of 290–370 nm; the low-refractive-index surface strengthening layer is made of Y2O3, Al2O3 or MgO; The total physical thickness of the single-period structure is controlled at 1165–1335 nm; The physical thickness of the high-refractive-index transition layer accounts for 1.93%–5.4% of the total thickness of the damage-resistant layer in a single cycle, and the total thickness of the low-refractive-index electric field isolation layer and the low-refractive-index surface strengthening layer accounts for more than 94% of the total thickness of the damage-resistant layer in a single cycle.
[0052] The core design feature of this layer is that the low refractive index layer dominates the absolute thickness, while the high refractive index layer is extremely thin.
[0053] In this embodiment, the dual-period structure of the damage-resistant layer L is composed of two sets of single-period structures superimposed to meet the laser damage suppression requirements under higher power density conditions. Regardless of whether a single-period or dual-period structure is used, the high-refractive-index layer is sandwiched between two low-refractive-index layers, forming a stable "low-high-low" sandwich configuration.
[0054] By employing the aforementioned extreme asymmetric thickness design, the peak laser electric field can be primarily confined within a low-absorption, high-damage-threshold low-refractive-index dielectric layer, while the ultrathin high-refractive-index layer remains in a weak-field region. This significantly reduces the optical field intensity and thermal accumulation effect within the high-refractive-index material. Simultaneously, the thick low-refractive-index dielectric layers on both sides effectively weaken abrupt changes in the optical field at the interface, reducing local optical field enhancement effects and the risk of defect-induced damage, thus achieving a synergistic effect of optical field distribution optimization and damage suppression.
[0055] This layer achieves the following technical effects through the synergy of material system design and asymmetric optical field modulation structure: (1) Peak isolation effect of electric field. By confining the main optical field energy inside the high-damage-threshold low-refractive-index medium, the light energy deposition and heat accumulation in high-refractive-index materials are effectively reduced, and the laser damage threshold of the film system is significantly improved; (2) Defect-induced damage suppression effect. The thickness of the ultrathin high-fold layer is greatly reduced, which can effectively reduce the amplification effect of nodules, microparticles and structural defects on the local optical field and reduce the probability of damage initiation point formation; (3) Interface smoothing and surface strengthening effects. Surface media such as Y2O3 and MgO can improve the surface smoothness of the film and modify micro-defects, while improving the hardness, wear resistance and environmental stability of the film, thereby improving the long-term service reliability of the film system; (4) Enhanced thermal stability. The synergistic effect of high thermal stability oxides and low absorption medium can reduce the accumulation of thermal stress under high power operation conditions and improve the long-term operational stability of the film.
[0056] All materials are preferably oxide materials with a purity of not less than 99%, and are prepared by electron beam evaporation, ion beam assisted deposition or magnetron sputtering processes to obtain high-quality thin films with dense uniformity and low defect density.
[0057] Among them, SiO2 has extremely low intrinsic absorption loss and excellent laser damage threshold in the 3–5 μm mid-infrared band, making it suitable as the main electric field carrier medium; ZrO2 and HfO2 have high refractive index, good thermal stability and low mid-infrared absorption loss, making them suitable as ultrathin high-refractive-index transition layers; Y2O3 has excellent mid-infrared transmittance, low absorption loss and good chemical stability, while also improving the surface smoothness and mechanical stability of the film; MgO has low refractive index, high thermal conductivity and excellent laser damage resistance, which can further enhance the thermal diffusion capability and high-power operation stability of the film.
[0058] Through the above-mentioned extremely asymmetric thickness ratio design, the peak value of the laser electric field is completely confined within the thick SiO2 medium with low absorption and high damage resistance. This ensures that the ultrathin ZrO2 high-refractive-index layer is always in a weak field region where the electric field intensity is less than 2% of the peak value. This completely avoids the risk of thermal damage to the high-refractive-index medium from the perspective of optical field distribution. At the same time, the thick Y2O3 passivation layer can effectively modify the micro-defects on the film surface and improve the surface hardness and wear resistance. The synergistic effect of the two significantly improves the overall laser damage threshold and long-term operational stability of the film system.
[0059] Preferred embodiment 1 The damage-resistant layer L adopts a single-cycle structure, and from the core reflective layer R to the moisture-proof protective layer M, the layers are as follows: 1. Pure SiO2 electric field isolation layer, thickness 867.72 nm, refractive index 1.3904; 2. Pure ZrO2 high-refractive-index transition layer, thickness 30.00 nm, refractive index 2.0350; 3. Pure Y2O3 surface passivation layer, thickness 295.37 nm, refractive index 1.7730.
[0060] The total physical thickness is 1193.09 nm.
[0061] Preferred embodiment 2 The damage-resistant layer L adopts a single-cycle structure, and from the core reflective layer R to the moisture-proof protective layer M, the layers are as follows: 1. Pure SiO2 electric field isolation layer, thickness 867.68nm; 2. Pure HfO2 high-refractive-index transition layer, thickness 30.00 nm; 3. Pure Y2O3 surface passivation layer, thickness 295.37nm.
[0062] The total physical thickness is 1193.05 nm.
[0063] This embodiment utilizes the low mid-infrared absorption loss and excellent chemical stability of HfO2 to further improve the long-term environmental reliability of the film while maintaining a high laser damage threshold.
[0064] Preferred Example 3 This damage-resistant layer L adopts a single-cycle structure, and from the core reflective layer R to the moisture-proof protective layer M, the layers are as follows: 1. Pure SiO2 electric field isolation layer, thickness 850.00 nm; 2. Pure ZrO2 high-refractive-index transition layer, thickness 30.00 nm; 3. Pure MgO surface reinforcement layer, thickness 330.00 nm.
[0065] The total physical thickness is 1210.00 nm.
[0066] This embodiment utilizes the high thermal conductivity and excellent laser damage resistance of MgO to enhance the thermal diffusion capability of the film and the high power operation stability, making it suitable for mid-infrared fiber laser output scenarios with higher power density.
[0067] (5) Moisture-Barrier Protective Layer M The moisture-proof protective layer M is disposed on the surface of the damage-resistant layer L, forming the outermost protective barrier to block moisture and pollutants. With efficient moisture blocking and optical matching of the air interface as its core functions, it weakens its resistance to laser damage, forming a clear functional division with the inner damage-resistant layer L, and is suitable for long-term stable operation in harsh environments such as high humidity, high heat, and high corrosion.
[0068] In this embodiment, the moisture-proof protective layer M adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure; The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3; The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5; The multilayer gradient composite structure comprises multiple layers of mixed SiO2 and metal oxides with different component ratios, each with a single-layer physical thickness of 30–80 nm; or multiple layers of pure oxide structures, each using Al2O3, HfO2, or Y2O3, with a single-layer physical thickness of 30–50 nm. Examples include Al2O3 / SiO2 composite structures, Al2O3 / Y2O3 / Al2O3 composite structures, or Al2O3 / HfO2 / Al2O3 composite structures. The Al2O3 / SiO2 composite structure is preferably a bilayer silicon-aluminum gradient composite stack. In addition to the above preferred options, the bilayer gradient composite stack can also be an HfO2-SiO2 system, with each single-layer thickness controlled at 30–80 nm. The aforementioned oxides all possess high density, low water vapor permeability, and excellent chemical stability, enabling them to form continuous, non-porous barrier structures. They effectively achieve long-term isolation of water vapor, corrosive media, and pollutants, while simultaneously achieving optical admittance matching at the air-film interface, reducing Fresnel reflection loss, and significantly enhancing the environmental tolerance of the optical fiber substrate.
[0069] The preferred embodiment employs a double-layer gradient composite stack, consisting of an aluminum-rich mixed layer (SiO2) from the inside out. 0.35 (Al2O3) 0.65 Silicon-rich hybrid layer (SiO2) 0.65 (Al2O3) 0.35 The inner aluminum-rich mixed phase has high density and extremely low porosity, forming a dense barrier that significantly inhibits the infiltration of water vapor and corrosive media, fulfilling the core moisture-proof protection function. Simultaneously, it forms a smooth refractive index transition with the inner damage-resistant layer L, ensuring continuous and stable interfacial bonding. The outer silicon-rich mixed phase has a refractive index close to that of air, enabling precise admittance matching at the air-film interface, effectively reducing Fresnel reflection loss and optimizing end-face optical transmission performance. The two layers exhibit a continuous and gradual change in composition, with the refractive index decreasing smoothly from the inside out, further enhancing the film's sealing and optical matching accuracy.
[0070] The conventional simplified embodiment can use a single layer of homogeneous Al2O3-SiO2 mixed oxide or a single layer of dense Al2O3, which can meet the basic moisture barrier, pollution prevention and simple optical matching requirements under normal working conditions. The structure is simple and the preparation is convenient. However, due to the lack of gradient transition advantage of the single-layer structure, its water vapor barrier limit and interface admittance matching effect are weaker than the double-layer gradient stacked structure.
[0071] The overall mechanism of this layer is as follows: Highly efficient moisture and pollution prevention: The dense oxide film can form a continuous, non-porous, and stable barrier, effectively blocking the penetration of water vapor and corrosive media in the air into the film system and optical fiber substrate, preventing the optical fiber substrate from deliquescing and corroding, the film layer from oxidizing and failing, and the optical performance from degrading. At the same time, it can block the adhesion of pollutants such as dust and oil, and maintain the cleanliness of the optical fiber substrate for a long time.
[0072] Air interface admittance matching optimization: By precisely controlling the composition ratio and optical thickness of the film layer, a smooth transition of refractive index between the inner film system and the air interface is achieved, optimizing the impedance matching of the air-film system interface, effectively reducing stray interface reflections, and reducing laser transmission loss.
[0073] Long-term environmental stability assurance: The all-oxide material has excellent chemical inertness and its structure remains stable under high temperature and high humidity conditions for a long time. There are no problems such as component migration or oxidation and deterioration. It can play a long-term and stable role in moisture protection and optical matching, ensuring the long-term reliable operation of laser devices.
[0074] This invention, through a multi-layer functional film system integrated architecture, simultaneously achieves multiple functions on a single fiber substrate, including efficient pump light transmission, precise mid-infrared laser reflection, gradient stress relief, enhanced interface bonding, laser damage protection, moisture and contamination prevention, and optical admittance matching. It effectively solves industry technical problems such as high optical absorption, prominent thermal effects, easy detachment due to film-substrate stress mismatch, and easy deliquescence failure of fluoride fibers in traditional mid-infrared fiber lasers. It provides a compact, simple, and engineering-feasible end-face resonator integrated solution for high-power, high-stability, and highly integrated 3–5μm mid-infrared all-fiber lasers.
[0075] In this embodiment, the all-oxide thin film is used as the input reflector or output coupler of the resonant cavity of a mid-infrared all-fiber laser; when used as an input reflector, the core reflective layer R has a reflectivity of 95%-99.5% for the 3600-4000nm wavelength band; when used as an output coupler, the core reflective layer R has a reflectivity of 60%-85% for the 3600-4000nm wavelength band.
[0076] When used as the input film, a multilayer TiTa2O5 / TiO2 / SiO2 / Al2O3 / silicon-aluminum mixture structure is designed to enable the end-face film to have high transmittance in the near-infrared pump band and high reflectivity in the mid-infrared laser band, thereby constructing a laser resonator input end face with high feedback efficiency and low heat loss.
[0077] When used as an output waterproof membrane, a multi-layer structure can be constructed using materials such as TiTa2O5 / SiO2 / Al2O3 / silicon-aluminum mixture to partially reflect (preferably 60%–85%) the 3600–4000 nm wavelength band. While ensuring effective laser output in the 3600–4000 nm wavelength band, it also achieves moisture-proof, pollution-proof, and laser-damage-resistant functions for the fiber optic substrate. This improves the environmental adaptability and long-term reliability of the laser output without introducing end caps or complex packaging structures.
[0078] This invention also provides a method for preparing a 3-5 μm mid-infrared all-fiber laser all-oxide thin film, which includes the following steps: Step 1, fiber substrate pretreatment and clamping: After cleaning and pretreatment of the fiber substrate, fix the fiber substrate in the fixture and smoothly install it into the vacuum coating cavity, so that the fiber substrate is perpendicular to the direction of the film evaporation beam to ensure the uniformity of the film thickness. Step 2: Evacuate the vacuum coating chamber to a preset vacuum level and pre-melt various oxide film materials respectively. The oxide film materials include materials for forming the bonding layer A, gradient stress buffer layer G, core reflective layer R, damage-resistant layer L and moisture-proof protective layer M. Step 3, Segmented Temperature-Controlled Deposition: Using a combination of electron beam evaporation and ion-assisted deposition, the bonding layer A, the gradient stress buffer layer G, the core reflective layer R, the damage-resistant layer L, and the moisture-proof protective layer M are deposited layer by layer from the inside out on the optical fiber substrate according to the preset all-oxide thin film structure to obtain the sample. During the deposition process, a segmented temperature control strategy is used to control the temperature of the optical fiber substrate to avoid the precipitation of optical fiber fixing colloid and contamination of the end face due to the increase in the temperature of the optical fiber substrate. Step 4, Vacuum Annealing and Stress Relief: After all film deposition is completed, the sample is subjected to in-situ vacuum annealing under vacuum conditions to release residual stress inside the film, reduce defect density, and further optimize film density. Step 5: After annealing, allow the sample to cool naturally to room temperature, break the vacuum, and remove the coated sample. This sample is the all-oxide film.
[0079] The all-oxide thin film described in this invention is prepared using electron beam evaporation-ion-assisted deposition technology. The entire process is completed in a DJ-800 vacuum coating system, which is equipped with an open 270° electron beam evaporation source and a K-12 Kaufman ion source. This system can achieve synergistic control of evaporation deposition and ion bombardment, significantly improving film density and interfacial adhesion performance.
[0080] Through the above preparation process, densification, low stress, and low defect growth of multilayer oxide films can be achieved, further improving the optical performance, structural stability, and resistance to laser damage of the films in the near-infrared pump band and mid-infrared laser band.
[0081] In this embodiment, the optical fiber substrate in step 1 is a quartz optical fiber or a fluoride optical fiber; the preset vacuum level in step 2 is 8 × 10⁻⁶. -3 Pa; The pre-melting treatment adopts a gradient heating method to fully release adsorbed water vapor and residual gas inside the film material; The segmented temperature control strategy in step 3 is as follows: when the temperature of the optical fiber substrate rises to the preset first temperature threshold (120℃), the deposition is paused, and the substrate is cooled to below the preset second temperature threshold (80℃) under continuous vacuum conditions, and then the deposition is resumed. This cycle is repeated until all film layers are deposited, thereby suppressing the accumulation of temperature on the optical fiber substrate and improving the stability and repeatability of the thin film structure. The second temperature threshold is lower than the first temperature threshold; The in-situ vacuum annealing temperature in step 4 is 200-400℃, the holding time is 1-3 hours, and the vacuum degree is maintained at 1×10 -3 Below Pa; after annealing, allow the sample to cool naturally to room temperature with the chamber at a cooling rate not exceeding 2℃ / min.
[0082] In this embodiment, step 3 employs a combination of electron beam evaporation and ion-assisted deposition for deposition. The deposition process is as follows: (1) When the bonding layer A is deposited, the deposition rate is 0.1-0.3 nm / s, the temperature of the optical fiber substrate is controlled at 80-120℃, and the bonding layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure or a multi-layer oxide composite structure. a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and the deposition thickness is 20-100nm; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, with a deposition thickness of 20-50 nm. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5. c. The multilayer oxide composite structure adopts a multilayer mixture of SiO2 and metal oxide with different component ratios. The molar ratio of SiO2 to metal oxide is controlled by controlling the electron beam evaporation rate. The total deposition thickness is 20-50 nm. (2) When depositing the gradient stress buffer layer G, three stepped gradient composite structures are deposited sequentially: The first layer is a low-refractive-index mixed layer with a refractive index of 1.50-1.70, a deposition thickness of 50-120 nm, and a deposition rate of 0.1-0.3 nm / s. This low-refractive-index mixed layer is either an aluminum-rich Al₂O₃-SiO₂ mixed layer or a yttrium-rich Y₂O₃-SiO₂ mixed layer, wherein the Al₂O₃ or Y₂O₃ content is 55-80 mol%, and the SiO₂ content is 20-45 mol%. The second layer is a medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90, a deposition thickness of 50-100 nm, and a deposition rate of 0.1-0.2 nm / s; the medium-refractive-index pure oxide layer is made of Al2O3, Y2O3, or HfO2. The third layer is a high refractive index matching layer with a refractive index of 1.90-2.30, a deposition thickness of 20-50 nm, and a deposition rate of 0.05-0.15 nm / s; the high refractive index matching layer is made of HfO2, ZrO2, Ta2O5, or TiO2. During the deposition of the three-layer stepped gradient composite structure, the ion source-assisted energy was 500-800 eV, and the ion beam current density was 50-100 μA / cm². 2 ; (3) When depositing the core reflective layer R, a method of alternating stacking of high-refractive-index oxide layers and low-refractive-index oxide layers is adopted. The high-refractive-index oxide layers are at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2, and Nb2O5, with a refractive index of 1.90-2.35, a single-layer deposition thickness of 200-700 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source assisted energy of 600-1000 eV. Among them, when depositing TiTa2O5, Ti-doped Ta2O5 is used, and the molar ratio of Ti doping is controlled to be 5%-20%. The low-refractive-index oxide layers are at least one of SiO2, Al2O3, MgO, and Y2O3, with a refractive index of 1.39-1.77, and a single-layer deposition thickness of 300-1000 nm. The deposition rate is 0.2-0.4 nm / s, and the ion source assisted energy is 300-500 eV. The thickness of each layer is optimized according to the preset mid-infrared standing wave field distribution. The total number of layers is 3-13, and the total thickness is 0.7-11.2 μm. (4) When depositing the damage-resistant layer L, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric single-period structure, or a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, a low-refractive-index surface passivation layer, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric double-period structure: The low-refractive-index electric field isolation layer is made of SiO2, with a deposition thickness of 850-900 nm, a deposition rate of 0.2-0.4 nm / s, and an ion source-assisted energy of 300-500 eV. The high refractive index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5, with a deposition thickness of 25-65 nm, a deposition rate of 0.05-0.15 nm / s, and an ion source assisted energy of 500-800 eV. The low-refractive-index surface passivation layer is made of Y2O3, Al2O3 or MgO, with a deposition thickness of 290-370 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source-assisted energy of 500-800 eV. During the deposition process, the temperature of the optical fiber substrate is controlled to not exceed 120℃; (5) When depositing the moisture-proof protective layer M, a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure is adopted; a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3; the deposition thickness is 100-150nm, the deposition rate is 0.1-0.2nm / s, and the ion source assisted energy is 500-800eV; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5, and the deposition thickness is 100–130 nm. c. The multilayer gradient composite structure is a mixture of SiO2 and metal oxides with different component ratios arranged in multiple layers, with a single layer deposition thickness of 30–80 nm; or a multilayer pure oxide structure, with each pure oxide structure using Al2O3, HfO2 or Y2O3, and a single layer deposition thickness of 30–50 nm.
[0083] Example 1 This embodiment presents a multi-band compatible end-face reflective film based on an AGRLM pentagonal composite structure, suitable for 3.7 μm erbium-doped fiber lasers, employing an all-oxide material system. The core design objective of this embodiment is to achieve a reflectivity of ≥95.5% in the 3730 nm operating band, while ensuring transmittance of ≥99% in the 976 nm and 1976 nm dual-pump bands, and ≥99% in the 2800 nm band. The film, from the fiber end face outwards, consists of an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M.
[0084] Among them, the bonding layer A adopts a single-layer silicon-rich Al2O3-SiO2 mixed oxide structure with a SiO2 to Al2O3 molar ratio of 0.65:0.35 and a physical thickness of 30.00 nm. A high-strength film-substrate interface is constructed through a silicon-oxygen-aluminum-oxygen composite bonding mechanism, providing a uniform nucleation substrate for subsequent film layers.
[0085] The gradient stress buffer layer G adopts a three-layer stepped gradient composite structure, which consists of the following layers from the inside out: 1. Aluminum-rich Al2O3-SiO2 mixed layer: the molar ratio of SiO2 to Al2O3 is 0.35:0.65, and the physical thickness is 80.00 nm; 2. Dense pure Al2O3 layer: physical thickness 70.00 nm; 3. HfO2 transition matching layer: physical thickness 30.00 nm.
[0086] By gradually changing the component ratio, a continuous and smooth transition in refractive index, coefficient of thermal expansion and mechanical modulus is achieved, releasing residual stress at the interface step by step, while completing the optical admittance pre-matching with the core reflective layer R.
[0087] Unlike traditional uniform λ / 4 symmetrical periodic stacked structures, the core reflective layer R employs a non-uniform thickness and differentiated high-refractive-index material matching design based on the mid-infrared standing wave field distribution. This layer uses TiTa2O5 as the main high-refractive-index material, supplemented by a TiO2 auxiliary high-refractive-index layer, and forms the core reflective layer together with a SiO2 low-refractive-index layer. The thickness of each layer is precisely optimized according to the laser standing wave field distribution, rather than uniformly using a λ / 4 optical thickness. In high-field-strength regions, low-absorption, highly stable TiTa2O5 material is preferentially used to fundamentally reduce light absorption and heat accumulation, while in low-field-strength regions, TiO2 material with a higher refractive index is introduced to optimize overall thermal stress and total film thickness while ensuring spectral performance. This design enables precise dual-spectral control of high transmittance in the near-infrared pump band and high reflectance in the 3–5 μm laser band, while maintaining extremely low intrinsic absorption and excellent thermal stability, significantly improving the laser damage threshold of the film system.
[0088] The damage-resistant layer L adopts a "low-high-low" sandwich-style single-cycle structure, consisting of the following layers from the inside out: 1. Pure SiO2 electric field isolation layer: physical thickness 867.68 nm; 2. Pure ZrO2 high-refractive-index transition layer: physical thickness 30.00 nm; 3. Pure Y2O3 surface passivation layer: physical thickness 295.37 nm.
[0089] By using an asymmetric thickness design, the peak value of the laser electric field is confined within the low-absorption, high-damage-resistance SiO2 layer, ensuring that the ZrO2 high-refractive-index layer is always in a region with a low electric field intensity. This completely avoids the risk of thermal damage to the high-refractive-index medium from the perspective of optical field distribution, and significantly improves the laser damage threshold of the film system.
[0090] Moisture-proof protective layer M uses two layers of Al2O3 The SiO2 gradient mixed oxide structure, from the inside out, consists of: 1. Aluminum-rich mixed layer: SiO2 to Al2O3 molar ratio is 0.35:0.65, physical thickness is 65.00 nm; 2. Silicon-rich hybrid layer: The molar ratio of SiO2 to Al2O3 is 0.65:0.35, and the physical thickness is 75.00 nm.
[0091] By gradually varying the component ratio, the refractive index decreases smoothly from the inside to the outside, optimizing the optical admittance matching of the air-film interface and effectively suppressing interface scattering loss. At the same time, relying on the structural advantages of the high density and low porosity of the silicon-aluminum mixed phase, the water vapor barrier and oxidation protection effects are enhanced, improving the fiber end face's resistance to deliquescence and ensuring the long-term environmental stability of the film system.
[0092] like Figure 3 As shown, the thin film has a transmittance of 99.89% and 99.95% in the pump bands of 976 nm and 1976 nm, respectively; a transmittance of 99.98% in the 2800 nm band; and a reflectance of 96.1% at 3730 nm, which meets the requirements for use in the end face resonator of mid-infrared all-fiber lasers.
[0093] Table 1. Membrane parameters for Example 1 Film layer sequence (from fiber end outwards) Membrane code Material composition Physical thickness (nm) Level 1 A <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 30.00 2nd floor G <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 80.00 3rd floor G <![CDATA[Al2O3]]> 70.00 4th floor G <![CDATA[HfO2]]> 30.00 5th floor R <![CDATA[TiTa2O5]]> 444.53 6th floor R <![CDATA[SiO2]]> 665.15 7th floor R <![CDATA[TiTa2O5]]> 498.64 8th floor R <![CDATA[SiO2]]> 646.98 9th floor R <![CDATA[TiO2]]> 466.25 10th floor R <![CDATA[SiO2]]> 624.65 11th floor R <![CDATA[TiO2]]> 499.95 12th floor R <![CDATA[SiO2]]> 629.18 13th floor R <![CDATA[TiTa2O5]]> 471.53 14th floor L <![CDATA[SiO2]]> 867.72 15th floor L <![CDATA[ZrO2]]> 30.00 16th floor L <![CDATA[Y2O3]]> 295.37 17th floor M <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 65.00 18th floor M <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 75.00 Example 2 This embodiment presents an end-face dichroic reflective film for a 4 μm mid-infrared all-fiber laser based on an AGRLM pentagonal composite structure, employing an all-oxide material system. Compared to Embodiment 1, this embodiment features: a bilayer composition-gradient structure for the adhesive layer A to further enhance the interfacial bonding between the film and the substrate; a yttrium-based gradient buffer system for the gradient stress buffer layer G to optimize the transition of interfacial properties; and a single-layer dense Al2O3 layer as a moisture-proof protective layer M to simplify the fabrication process. Designed for the 4 μm input mirror application requirements, this embodiment aims to achieve a high reflectivity of no less than 97% in the 3920 nm operating band, while ensuring transmittance of no less than 99% in both the 888 nm and 1645 nm dual-pump bands. The film, from the fiber end-face outwards, consists of the adhesive layer A, the gradient stress buffer layer G, the core reflective layer R, the damage-resistant layer L, and the moisture-proof protective layer M.
[0094] The adhesive layer A adopts a two-layer composition gradient structure, consisting of silicon-rich (SiO2) layers from the fiber substrate outwards. 0.65 (Al2O3) 0.35 Transition layer and equimolar ratio (SiO2) 0.50 (Al2O3) 0.50 The hybrid layers have physical thicknesses of 20.00 nm and 25.00 nm, respectively, for a total thickness of 45.00 nm. Through a continuous gradient of silicon and aluminum composition, a smooth transition between the optical fiber substrate and subsequent films is achieved, effectively improving interfacial bonding stability, reducing interfacial defect density, and providing a uniform and dense nucleation growth interface for subsequent films.
[0095] The gradient stress buffer layer G adopts a yttrium-based three-layer stepped gradient structure, with yttrium-rich (SiO2) layers from the inside out. 0.35 (Y2O3) 0.65 The mixture layer, the dense pure Y₂O₃ layer, and the HfO₂ transition matching layer have physical thicknesses of 70.00 nm, 60.00 nm, and 30.00 nm, respectively, for a total thickness of 160.00 nm. The yttrium-rich mixture layer ensures a smooth transition with the silicon-rich component of the binder layer. The pure Y₂O₃ layer exhibits excellent mid-infrared transmittance, chemical stability, and mechanical stability. The HfO₂ transition layer provides good refractive index matching with the high-refractive-index material of the core reflective layer. The three layers, through a gradual transition in refractive index, coefficient of thermal expansion, and mechanical properties, effectively alleviate residual stress at the interface and improve the structural stability and film quality of the subsequent core reflective layer.
[0096] The core reflective layer R employs the same non-uniform thickness optimization design as in Example 1, using Ti-doped Ta₂O₅ as the primary high-refractive-index material, supplemented by a TiO₂ auxiliary high-refractive-index layer and a SiO₂ low-refractive-index layer to construct a multi-layer reflective structure. The thickness of each layer is optimized based on the mid-infrared standing wave field distribution, rather than using a traditional λ / 4 optical thickness periodic structure. In high-field-strength regions, low-absorption, high-stability Ti-doped Ta₂O₅ material is preferentially used to reduce absorption loss and heat accumulation; in low-field-strength regions, TiO₂ material with a higher refractive index is introduced to further compress the film thickness while maintaining spectral performance. This design enables precise dual-spectral control of high transmission in the near-infrared dual-pump band and high reflectivity in the 3–5 μm mid-infrared working band, while maintaining excellent thermal stability and resistance to laser damage.
[0097] The structure, material composition and thickness parameters of the damage-resistant layer L are the same as those in Example 1. It adopts a "low-high-low" sandwich-type extreme asymmetric structure and achieves high-power laser damage protection function through electric field peak isolation design, thereby further improving the overall laser damage threshold and long-term operational reliability of the film system.
[0098] The moisture-proof protective layer M adopts a single-layer dense Al2O3 thin film structure with a physical thickness of 122.48 nm. Al2O3 has excellent chemical stability, environmental stability, and dense film-forming properties, which can form a continuous non-porous protective barrier on the outermost side of the membrane system, effectively preventing the diffusion of water vapor, corrosive media, and environmental pollutants into the membrane layer, while also taking into account the admittance matching effect of the air interface, thereby improving the long-term service stability of the membrane system under complex environmental conditions.
[0099] like Figure 4 As shown, the thin film in this embodiment achieves a transmittance of over 99.5% in both the 888 nm and 1645 nm pump bands, and a reflectance of 97.13% at the 3920 nm operating wavelength, which can meet the comprehensive performance requirements of high transmission, high reflection and high reliability of the input mirror at the end face of a 4 μm mid-infrared all-fiber laser.
[0100] Table 2. Membrane parameters for Example 2 Film layer sequence (from fiber end outwards) Membrane code Material composition Physical thickness (nm) Level 1 A <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 20.00 2nd floor A <![CDATA[(SiO2) 0.50 (Al2O3) 0.50 ]]> 25.00 3rd floor G <![CDATA[(SiO2) 0.35 (Y2O3) 0.65 ]]> 70.00 4th floor G <![CDATA[Y2O3]]> 60.00 5th floor G <![CDATA[HfO2]]> 30.00 6th floor R <![CDATA[TiTa2O5]]> 433.46 7th floor R <![CDATA[SiO2]]> 681.46 8th floor R <![CDATA[TiTa2O5]]> 487.63 9th floor R <![CDATA[SiO2]]> 654.45 10th floor R <![CDATA[TiO2]]> 467.68 11th floor R <![CDATA[SiO2]]> 641.25 12th floor R <![CDATA[TiO2]]> 460.99 13th floor R <![CDATA[SiO2]]> 642.95 14th floor R <![CDATA[TiTa2O5]]> 472.99 15th floor L <![CDATA[SiO2]]> 867.68 16th floor L <![CDATA[ZrO2]]> 30.00 17th floor L <![CDATA[Y2O3]]> 295.37 18th floor M <![CDATA[Al2O3]]> 122.48 Example 3 This embodiment presents an end-face dichroic reflective film for a 4 μm mid-infrared all-fiber laser based on an AGRLM pentagonal composite structure, employing an all-oxide material system. Key features of this embodiment include: a core reflective layer using a pure TiTa2O5 / SiO2 binary material system to simplify the fabrication process; a damage-resistant layer using a SiO2 / ZrO2 / MgO combination, with MgO selected as the surface strengthening layer to enhance heat dissipation and damage resistance; and a moisture-proof protective layer using an Al2O3 / HfO2 / Al2O3 three-layer composite structure to improve protection performance under extreme corrosive environments. The core design objective of this embodiment is to achieve a high reflectivity of ≥96% in the 3920 nm operating band, while ensuring a transmittance of ≥99% in the 888 nm and 1645 nm dual-pump bands. The film, from the fiber end-face outwards, consists of an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M.
[0101] The structure, composition, and thickness parameters of the adhesive layer A and the gradient stress buffer layer G are the same as those in Example 1, which together achieve high-strength film-substrate bonding and gradual release of residual stress at the interface.
[0102] Unlike traditional uniform λ / 4 symmetrical periodic stacked structures, the core reflective layer R employs a non-uniform thickness pure binary oxide matching design based on the mid-infrared standing wave field distribution. This layer uses only TiTa2O5 as a high-refractive-index material, forming the core reflective layer together with the low-refractive-index SiO2 layer. The thickness of each layer is precisely optimized according to the laser standing wave field distribution, rather than uniformly using a λ / 4 optical thickness. The TiTa2O5 used combines high refractive index, low intrinsic mid-infrared absorption, and excellent resistance to laser damage, allowing for precise control of the optical phase and reflection characteristics in the mid-infrared band. The SiO2 material is technologically mature and has excellent optical compatibility. The two materials work together to achieve target spectral control. Compared to multi-component film systems containing TiO2, the core reflective region material system in this embodiment is simplified, reducing the types of high-refractive-index film materials, lowering the risk of material interface compatibility and process complexity, and improving the stability of film preparation. At the same time, it avoids the performance drift problem caused by stress differences between multiple materials.
[0103] The damage-resistant layer L adopts a "low-high-low" sandwich-style single-cycle structure. From the core reflective layer R to the moisture-proof protective layer M, it consists of: a pure SiO2 electric field isolation layer with a thickness of 850.00 nm; a pure ZrO2 high-refractive-index transition layer with a thickness of 30.00 nm; and a pure MgO surface strengthening layer with a thickness of 330.00 nm. The total physical thickness is 1210.00 nm. Through asymmetric thickness design, the peak laser electric field is confined within the low-absorption, high-damage-resistant SiO2 layer, ensuring that the ZrO2 high-refractive-index layer is always in a region with a low electric field intensity, thus completely avoiding the risk of thermal damage to the high-refractive-index medium from the perspective of optical field distribution. This embodiment utilizes the high thermal conductivity and excellent laser damage tolerance of MgO to enhance the thermal diffusion capability and high-power operation stability of the film, making it suitable for mid-infrared fiber laser output scenarios with higher power density.
[0104] The moisture-proof protective layer M adopts a three-layer composite structure of Al2O3 / HfO2 / Al2O3, consisting of the following layers from the inside out: an inner dense Al2O3 layer with a physical thickness of 40.00 nm; a middle HfO2 barrier layer with a physical thickness of 50.00 nm; and an outer dense Al2O3 layer with a physical thickness of 30.00 nm. The total physical thickness is 120.00 nm. This structure forms a "dense-high barrier-dense" sandwich-like protective architecture. Relying on the extremely strong chemical inertness and ultra-high density of HfO2, it forms a dense and reliable triple protective barrier, significantly improving corrosion resistance and moisture barrier capabilities, making it suitable for high-corrosion, high-humidity, and high-temperature extreme environments such as marine and chemical industries. Simultaneously, the inner layer and the damage-resistant layer have a strong interface bond, the outer layer is wear-resistant and scratch-resistant, the overall refractive index transition is smooth, and the interface reflection loss is extremely low, having no significant impact on the overall spectral performance of the film system.
[0105] As shown in Figure 5, the spectrum of the thin film matches the design specifications well: the transmittance in the pump bands of 888 nm and 1645 nm reaches 99.1% and 99.4% respectively, and the reflectance at 3920 nm is 96.52%, which fully meets the engineering application requirements of the input mirror of the end face resonator of the mid-infrared all-fiber laser in a highly corrosive environment.
[0106] Table 3. Membrane Parameter Table for Example 3 Film layer sequence (from fiber end outwards) Membrane code Material composition Physical thickness (nm) Level 1 A <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 30.00 2nd floor G <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 80.00 3rd floor G <![CDATA[Al2O3]]> 70.00 4th floor G <![CDATA[HfO2]]> 30.00 5th floor R <![CDATA[TiTa2O5]]> 404.83 6th floor R <![CDATA[SiO2]]> 888.66 7th floor R <![CDATA[TiTa2O5]]> 382.32 8th floor R <![CDATA[SiO2]]> 850.54 9th floor R <![CDATA[TiTa2O5]]> 365.49 10th floor R <![CDATA[SiO2]]> 848.5 11th floor R <![CDATA[TiTa2O5]]> 365.14 12th floor R <![CDATA[SiO2]]> 911.56 13th floor R <![CDATA[TiTa2O5]]> 249.45 14th floor R <![CDATA[SiO2]]> 926.43 15th floor R <![CDATA[TiTa2O5]]> 387.90 16th floor L <![CDATA[SiO2]]> 850.00 17th floor L <![CDATA[ZrO2]]> 30.00 18th floor L MgO 330.00 19th floor M <![CDATA[Al2O3]]> 40.00 20th floor M <![CDATA[HfO2]]> 50.00 21st floor M <![CDATA[Al2O3]]> 30.00 Example 4 This embodiment presents an end-face dichroic reflective film for a 4 μm mid-infrared all-fiber laser based on an AGRLM pentagonal composite structure, employing an all-oxide material system. Compared to previous embodiments, the core innovation of this embodiment lies in the following: the core reflective layer R adopts a gradient composite design with a symmetrical refractive index variation trend of Ta2O5-TiTa2O5-TiO2, achieving a smooth refractive index transition from the substrate to the film center and then to the air end; the high-refractive-index material of the damage-resistant layer L is simultaneously replaced with HfO2, precisely connecting with the gradient refractive index distribution of the core reflective layer, constructing a continuous refractive index profile without abrupt changes from the substrate to the air interface. The core design goal of this embodiment is to achieve a high reflectivity of ≥97% in the 3920 nm operating band, while ensuring a transmittance of ≥99.5% in the 888 nm and 1645 nm dual-pump bands, and forming a flat high-reflectivity band in the 3850~4000 nm band. The thin film consists of, from the optical fiber end outwards, an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M.
[0107] The structure, composition, and thickness parameters of the adhesive layer A and the gradient stress buffer layer G are the same as those in Example 1, which together achieve high-strength film-substrate bonding and gradual release of residual stress at the interface.
[0108] The core reflective layer R differs from the traditional uniform λ / 4 symmetrical periodic stacking structure and single high-refractive-index material design. It adopts a non-uniform thickness and refractive index gradient symmetrical composite design based on the mid-infrared standing wave field distribution. This layer strictly follows the gradient law of "low refractive index on the substrate side → high refractive index at the center of the film system → low refractive index on the air side": from the substrate side to the center of the film system, the refractive index of the high-refractive-index material gradually increases, successively using Ta2O5 (n≈2.10), TiTa2O5 (n≈2.20), and TiO2 (n≈2.30) as high-refractive-index layers; from the center of the film system to the air side, the refractive index of the high-refractive-index material gradually decreases, successively using TiTa2O5 and Ta2O5 as high-refractive-index layers, while the low-refractive-index layer uniformly uses SiO2 (n≈1.39). The thickness of each layer is precisely optimized according to the laser standing wave field distribution rather than uniformly using λ / 4 optical thickness.
[0109] This layer achieves multiple technical effects through this continuous gradient refractive index design: 1. Significantly alleviates interfacial stress concentration: The refractive index difference between adjacent high refractive index layers is controlled within 0.2, which smooths the abrupt changes in optical and thermal properties between film layers, making the residual stress at the interface continuously distributed rather than concentrated and abrupt, greatly improving the thermal cycling resistance of the film system, and significantly suppressing the performance drift and film peeling risk during long-term use. 2. Effectively reduces interface scattering loss: The continuous gradient refractive index distribution eliminates the large number of abrupt refractive index interfaces present in traditional film systems, making the propagation of light inside the film layer smoother, significantly reducing interface scattering loss, and further improving the transmittance of the pump band and the reflectivity of the laser band. 3. Achieving ultra-flat broadband high reflectivity: Compared with the design of a single high refractive index material, this gradient structure can achieve a flat high reflectivity band with minimal reflectivity fluctuation over a wider wavelength range, and the reflectivity spectrum edge is steeper with a higher out-of-band suppression ratio, which can more accurately suppress parasitic oscillations; 4. Material optimization in high field strength regions: TiTa2O5 material with low absorption and high stability is preferentially used in the region with the strongest electric field at the center of the film system to reduce light absorption and heat accumulation from the source, thus taking into account both spectral performance and resistance to laser damage.
[0110] All materials used are mature oxide film materials, which are compatible with conventional electron beam evaporation-ion assisted deposition processes, and the process is highly versatile.
[0111] The damage-resistant layer L adopts a "low-high-low" sandwich-style single-cycle structure, consisting of the following layers from the inside out: 1. SiO2 electric field isolation layer: physical thickness 859.56 nm; 2. HfO2 high-refractive-index transition layer: physical thickness 60.76 nm; 3. Y2O3 surface passivation layer: physical thickness 368.04 nm.
[0112] By employing an asymmetric thickness design, the peak laser electric field is confined within a low-absorption, high-damage-resistance SiO2 layer, placing the HfO2 high-refractive-index layer within a weak electric field range. This reduces the probability of thermal damage to the high-refractive-index medium from the perspective of the optical field structure. The refractive index of HfO2 and the outer Ta2O5 layer exhibit a gradual change, and the surface Y2O3 layer can also smoothly match the outer moisture-proof layer. This contributes to a smooth refractive index transition throughout the entire film system, mitigating abrupt interface changes and reducing interface stress and scattering loss.
[0113] The moisture-proof protective layer M adopts a simplified double-layer silicon-aluminum gradient mixed oxide structure, which consists of the following layers from the inside out: 1. Aluminum-rich mixed layer: SiO2 to Al2O3 molar ratio is 0.35:0.65, physical thickness is 30.00 nm; 2. Silicon-rich hybrid layer: The molar ratio of SiO2 to Al2O3 is 0.65:0.35, and the physical thickness is 35.00 nm.
[0114] By gradually changing the component ratio, the refractive index decreases smoothly from the inside to the outside, eventually transitioning to the air refractive index. This optimizes the optical admittance matching of the air-film interface, effectively suppresses interface scattering loss, and meets the water vapor barrier requirements under normal operating conditions.
[0115] As shown in Figure 6, optical simulation verified that the transmittance of the thin film reaches 99.9% and 99.8% in the pump bands of 888 nm and 1645 nm, respectively, and the reflectance at 3920 nm is 97.64%. A flat high-reflection band is formed in the 3850~4000 nm band, and the edge of the reflection spectrum is steep, providing a reliable technical solution for the engineering application of thin films on the end face of all-fiber lasers.
[0116] Table 4. Membrane Parameter Table for Example 4 Film layer sequence (from fiber end outwards) Membrane code Material composition Physical thickness (nm) Level 1 A <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 30.00 2nd floor G <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 80.00 3rd floor G <![CDATA[Al2O3]]> 70.00 4th floor G <![CDATA[HfO2]]> 30.00 5th floor R <![CDATA[Ta2O5]]> 402.01 6th floor R <![CDATA[SiO2]]> 821.61 7th floor R <![CDATA[TiTa2O5]]> 384.94 8th floor R <![CDATA[SiO2]]> 804.35 9th floor R <![CDATA[TiTa2O5]]> 410.83 10th floor R <![CDATA[SiO2]]> 673.80 11th floor R <![CDATA[TiO2]]> 403.84 12th floor R <![CDATA[SiO2]]> 692.76 13th floor R <![CDATA[TiTa2O5]]> 448.16 14th floor R <![CDATA[SiO2]]> 973.77 15th floor R <![CDATA[TiTa2O5]]> 471.04 16th floor R <![CDATA[SiO2]]> 603.13 17th floor R <![CDATA[Ta2O5]]> 352.90 18th floor L <![CDATA[SiO2]]> 859.56 19th floor L <![CDATA[HfO2]]> 60.76 20th floor L <![CDATA[Y2O3]]> 368.04 21st floor M <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 30.00 22nd floor M <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 35.00 Example 5 This embodiment presents a partial reflection output coupling film for a 4 μm mid-infrared all-fiber laser based on an AGRLM five-element composite structure, employing an all-oxide material system. Compared to the previous high-reflectivity resonant cavity input mirror embodiment, this embodiment features: a simplified fabrication using a single-layer dense Al2O3 adhesive layer; and a streamlined TiTa2O5 / SiO2 binary material system for the core reflector, significantly reducing the total number of film layers. It is specifically designed for controllable partial reflection output coupling in the 3920 nm band. The core design goal of this embodiment is to achieve a stable partial reflectivity of 50%-75% in the 3920 nm operating band. The film, from the fiber end outwards, consists of an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M.
[0117] In this example, the adhesive layer A is a single-layer dense Al2O3 film with a thickness of 30.00 nm; the structure, composition and thickness parameters of the gradient stress buffer layer G are the same as those in Example 1, which together achieve high-strength film-substrate bonding and gradual release of residual stress at the interface.
[0118] The core reflective layer R employs a non-uniform thickness pure binary oxide matching design based on the mid-infrared standing wave field distribution. This layer uses only TiTa2O5 as the high-refractive-index material, which, together with the SiO2 low-refractive-index layer, forms the core output reflective layer. The thickness of each layer is precisely optimized according to the laser standing wave field distribution, rather than using a uniform λ / 4 optical thickness. This significantly reduces the total number of film layers, simplifying the fabrication process while ensuring optical performance. The TiTa2O5 used combines high refractive index, low intrinsic mid-infrared absorption, and excellent resistance to laser damage, allowing for precise control of the optical phase and reflection characteristics in the 3920 nm band, achieving stable resonant cavity output coupling.
[0119] The damage-resistant layer L adopts a "low-high-low" sandwich-style single-cycle structure, consisting of the following layers from the inside out: 1. SiO2 electric field isolation layer: physical thickness 886.86 nm; 2. ZrO2 high-refractive-index transition layer: physical thickness 30.00 nm; 3. Y2O3 surface passivation layer: physical thickness 339.59 nm.
[0120] The moisture-proof protective layer M adopts a double-layer silicon-aluminum gradient mixed oxide structure, which consists of the following layers from the inside out: 1. Aluminum-rich mixed layer: SiO2 to Al2O3 molar ratio is 0.35:0.65, physical thickness is 50.00 nm; 2. Silicon-rich hybrid layer: The molar ratio of SiO2 to Al2O3 is 0.65:0.35, and the physical thickness is 60.00 nm.
[0121] As shown in Figure 7, optical simulation verified that the reflectivity of the end-face output film is stable at 72.14% in the 3920 nm mid-infrared laser band, which meets the design requirements for resonant cavity output coupling. After integrating it into the resonant cavity of the mid-infrared all-fiber laser, it can effectively replace the traditional discrete output mirror, simplify the resonant cavity structure, improve the system integration and operational reliability, and provide a compact and reliable output coupling scheme for the engineering application of all-fiber mid-infrared laser systems.
[0122] Table 5. Membrane Parameter Table for Example 5 Film layer sequence (from fiber end outwards) Membrane code Material composition Physical thickness (nm) Level 1 A <![CDATA[Al2O3]]> 30.00 2nd floor G <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 80.00 3rd floor G <![CDATA[Al2O3]]> 70.00 4th floor G <![CDATA[HfO2]]> 30.00 5th floor R <![CDATA[TiTa2O5]]> 547.37 6th floor R <![CDATA[SiO2]]> 578.14 7th floor R <![CDATA[TiTa2O5]]> 438.63 8th floor L <![CDATA[SiO2]]> 886.86 9th floor L <![CDATA[ZrO2]]> 30.00 10th floor L <![CDATA[Y2O3]]> 339.59 11th floor M <![CDATA[(SiO2) 0.35 (Al2O3) 0.65 ]]> 50.00 12th floor M <![CDATA[(SiO2) 0.65 (Al2O3) 0.35 ]]> 60.00 The above description is only a part of the embodiments of the present invention and does not limit the scope of protection of the present invention. Any equivalent device or equivalent process transformation made based on the content of the present invention specification and drawings, or direct or indirect application in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A 3-5 μm mid-infrared all-fiber laser all-oxide thin film, characterized in that, The all-oxide film is disposed on the optical fiber substrate and includes, in sequence from the direction closest to the optical fiber substrate to the direction furthest from the optical fiber substrate: an adhesive layer A, a gradient stress buffer layer G, a core reflective layer R, a damage-resistant layer L, and a moisture-proof protective layer M. The adhesive layer A is disposed on the optical fiber substrate to enhance the interfacial bonding stability between the film layer and the optical fiber substrate. The gradient stress buffer layer G is disposed on the surface of the adhesive layer A, and its refractive index increases gradually from the inside to the outside. It is used to achieve a smooth transition of optical and physical parameters to release residual stress at the interface. The core reflective layer R is disposed on the surface of the gradient stress buffer layer G and adopts a periodic structure of alternating stacks of high refractive index oxide layers and low refractive index oxide layers to achieve high transmission in the near-infrared pump band and reflection in the mid-infrared laser band. The damage-resistant layer L is disposed on the surface of the core reflective layer R and adopts an asymmetric single-period or double-period structure consisting of a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer. It is used to confine the laser electric field peak within the low-absorption medium layer to improve the laser damage resistance. The moisture-proof protective layer M is disposed on the surface of the damage-resistant layer L, forming the outermost protective barrier to block moisture and pollutants.
2. The 3-5μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The adhesive layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer oxide composite structure. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and has a physical thickness of 20-50nm. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide with a physical thickness of 20-50 nm. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5. The multilayer oxide composite structure consists of multiple layers of mixed SiO2 and metal oxide with different component ratios arranged sequentially, with a total physical thickness of 20-50 nm.
3. The 3-5μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The gradient stress buffer layer G adopts a three-layer stepped gradient composite structure with a total physical thickness of 120-270nm, and from the inside out are: A low-refractive-index hybrid layer has a refractive index of 1.50-1.70 and a physical thickness of 50-120 nm; the low-refractive-index hybrid layer is an aluminum-rich Al2O3-SiO2 hybrid layer or a yttrium-rich Y2O3-SiO2 hybrid layer, wherein the Al2O3 or Y2O3 content is 55-80 mol%, and the SiO2 content is 20-45 mol%. A medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90 and a physical thickness of 50-100 nm; the medium-refractive-index pure oxide layer is made of Al₂O₃, Y₂O₃, or HfO₂; and A high refractive index matching layer, with a refractive index of 1.90-2.30 and a physical thickness of 20-50 nm, is used to achieve refractive index matching with the high refractive index oxide layer of the core reflective layer R; the high refractive index matching layer adopts HfO2, ZrO2, Ta2O5 or TiO2.
4. The 3-5μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The core reflective layer R has a total of 3–13 layers and a total thickness of 0.7–11.2 μm. It is arranged in a symmetrical or approximately symmetrical manner with a high-refractive-index oxide layer or a low-refractive-index oxide layer as the center and a high-refractive-index oxide layer as the outermost layer. The symmetrical arrangement means that the high-refractive-index oxide layer and the low-refractive-index oxide layer adopt a symmetrical structure and use the same material at the symmetrical position. The approximately symmetrical arrangement means that the high-refractive-index oxide layer and the low-refractive-index oxide layer adopt a symmetrical structure and use different materials at the symmetrical position. The high-refractive-index oxide layer is made of at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2, and Nb2O5, with a refractive index of 1.90–2.35 and a single-layer physical thickness of 200–700 nm; wherein the molar doping ratio of Ti in the TiTa2O5 is 5%–20%; The low-refractive-index oxide layer is made of at least one of SiO2, Al2O3, MgO and Y2O3, with a refractive index of 1.39–1.77 and a single-layer physical thickness of 300–1000 nm.
5. The 3-5 μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The single-period structure in the damage-resistant layer L, from the inside out, includes: A low-refractive-index electric field isolation layer with a physical thickness of 850–900 nm is used; the low-refractive-index electric field isolation layer is made of SiO2. A high-refractive-index transition layer with a physical thickness of 25–65 nm; the high-refractive-index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5; A low-refractive-index surface strengthening layer with a physical thickness of 290–370 nm; the low-refractive-index surface strengthening layer is made of Y2O3, Al2O3 or MgO; The total physical thickness of the single-period structure is controlled at 1165–1335 nm; The physical thickness of the high-refractive-index transition layer accounts for 1.93%–5.4% of the total thickness of the damage-resistant layer in a single cycle, and the total thickness of the low-refractive-index electric field isolation layer and the low-refractive-index surface strengthening layer accounts for more than 94% of the total thickness of the damage-resistant layer in a single cycle. The dual-period structure of the damage-resistant layer L is composed of two sets of single-period structures superimposed on each other.
6. The 3-5μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The moisture-proof protective layer M adopts a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure. The monolayer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and the physical thickness of the monolayer is 100–130 nm. The monolayer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5, and the physical thickness of the monolayer is 100–130 nm. The multilayer gradient composite structure is a mixed layer of SiO2 and metal oxide with different component ratios arranged in multiple layers, with a single layer physical thickness of 30–80 nm; or a pure oxide structure arranged in multiple layers, with each pure oxide structure using Al2O3, HfO2 or Y2O3, and a single layer physical thickness of 30–50 nm.
7. The 3-5 μm mid-infrared all-fiber laser all-oxide thin film as described in claim 1, characterized in that, The all-oxide thin film is used as the input reflector or output coupler of the resonant cavity of a mid-infrared all-fiber laser; when used as an input reflector, the core reflective layer R has a reflectivity of 95%-99.5% in the 3600-4000nm band; when used as an output coupler, the core reflective layer R has a reflectivity of 60%-85% in the 3600-4000nm band.
8. A method for preparing a 3-5 μm mid-infrared all-fiber laser all-oxide thin film, characterized in that, The method for preparing the all-oxide thin film as described in any one of claims 1-7 comprises the following steps: Step 1: After cleaning and pre-treating the fiber substrate, fix the fiber substrate in the fixture and smoothly install it into the vacuum coating cavity, so that the fiber substrate is perpendicular to the direction of the film evaporation beam. Step 2: Evacuate the vacuum coating chamber to a preset vacuum level and pre-melt various oxide film materials respectively. The oxide film materials include materials for forming the bonding layer A, gradient stress buffer layer G, core reflective layer R, damage-resistant layer L and moisture-proof protective layer M. Step 3: According to the preset all-oxide thin film structure, the bonding layer A, the gradient stress buffer layer G, the core reflective layer R, the damage resistance layer L and the moisture-proof protective layer M are deposited layer by layer from the inside to the outside on the optical fiber substrate to obtain a sample. During the deposition process, a segmented temperature control strategy is adopted to control the temperature of the optical fiber substrate. Step 4: After all film layers have been deposited, the sample is subjected to in-situ vacuum annealing under vacuum conditions to release residual stress inside the film layers. Step 5: After annealing, allow the sample to cool naturally to room temperature, break the vacuum, and remove the coated sample. This sample is the all-oxide film.
9. The method for preparing a 3-5 μm mid-infrared all-fiber laser all-oxide thin film as described in claim 8, characterized in that, In step 1, the optical fiber substrate is either a quartz optical fiber or a fluoride optical fiber; in step 2, the preset vacuum level is 8 × 10⁻⁶. - 3 Pa; The pre-melting treatment adopts a gradient heating method to fully release adsorbed water vapor and residual gas inside the film material; The segmented temperature control strategy in step 3 is as follows: when the temperature of the optical fiber substrate rises to the preset first temperature threshold, the deposition is paused, and the substrate is cooled to below the preset second temperature threshold under continuous vacuum conditions, and then the deposition is resumed. This cycle is repeated until all film layers are deposited, wherein the second temperature threshold is less than the first temperature threshold; The in-situ vacuum annealing temperature in step 4 is 200-400℃, the holding time is 1-3 hours, and the vacuum degree is maintained at 1×10 -3 Below Pa; after annealing, allow the sample to cool naturally to room temperature with the chamber at a cooling rate not exceeding 2℃ / min.
10. The method for preparing a 3-5 μm mid-infrared all-fiber laser all-oxide thin film as described in claim 8, characterized in that, In step 3, a combination of electron beam evaporation and ion-assisted deposition is used for deposition. The deposition process is as follows: (1) When the bonding layer A is deposited, the deposition rate is 0.1-0.3 nm / s, the temperature of the optical fiber substrate is controlled at 80-120℃, and the bonding layer A adopts a single-layer pure oxide structure, a single-layer mixed oxide structure or a multi-layer oxide composite structure. a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3, and the deposition thickness is 20-50nm; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, with a deposition thickness of 20-50 nm. The metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5. c. The multilayer oxide composite structure adopts a multilayer mixture of SiO2 and metal oxide with different component ratios. The molar ratio of SiO2 to metal oxide is controlled by controlling the electron beam evaporation rate. The total deposition thickness is 20-50 nm. (2) When depositing the gradient stress buffer layer G, three stepped gradient composite structures are deposited sequentially: The first layer is a low-refractive-index mixed layer with a refractive index of 1.50-1.70, a deposition thickness of 50-120 nm, and a deposition rate of 0.1-0.3 nm / s. This low-refractive-index mixed layer is either an aluminum-rich Al₂O₃-SiO₂ mixed layer or a yttrium-rich Y₂O₃-SiO₂ mixed layer, wherein the Al₂O₃ or Y₂O₃ content is 55-80 mol%, and the SiO₂ content is 20-45 mol%. The second layer is a medium-refractive-index pure oxide layer with a refractive index of 1.65-1.90, a deposition thickness of 50-100 nm, and a deposition rate of 0.1-0.2 nm / s; the medium-refractive-index pure oxide layer is made of Al2O3, Y2O3, or HfO2. The third layer is a high refractive index matching layer with a refractive index of 1.90-2.30, a deposition thickness of 20-50 nm, and a deposition rate of 0.05-0.15 nm / s; the high refractive index matching layer is made of HfO2, ZrO2, Ta2O5, or TiO2. During the deposition of the three-layer stepped gradient composite structure, the ion source-assisted energy was 500-800 eV, and the ion beam current density was 50-100 μA / cm². 2 ; (3) When depositing the core reflective layer R, a method of alternating stacking of high-refractive-index oxide layers and low-refractive-index oxide layers is adopted. The high-refractive-index oxide layers are at least one of TiTa2O5, TiO2, Ta2O5, ZrO2, HfO2, and Nb2O5, with a refractive index of 1.90-2.35, a single-layer deposition thickness of 200-700 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source assisted energy of 600-1000 eV. Among them, when depositing TiTa2O5, Ti-doped Ta2O5 is used, and the molar ratio of Ti doping is controlled to be 5%-20%. The low-refractive-index oxide layers are at least one of SiO2, Al2O3, MgO, and Y2O3, with a refractive index of 1.39-1.77, and a single-layer deposition thickness of 300-1000 nm. The deposition rate is 0.2-0.4 nm / s, and the ion source assisted energy is 300-500 eV. The thickness of each layer is optimized according to the preset mid-infrared standing wave field distribution. The total number of layers is 3-13, and the total thickness is 0.7-11.2 μm. (4) When depositing the damage-resistant layer L, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric single-period structure, or a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, a low-refractive-index surface passivation layer, a low-refractive-index electric field isolation layer, a high-refractive-index transition layer, and a low-refractive-index surface passivation layer are deposited sequentially to form an asymmetric double-period structure: The low-refractive-index electric field isolation layer is made of SiO2, with a deposition thickness of 850-900 nm, a deposition rate of 0.2-0.4 nm / s, and an ion source-assisted energy of 300-500 eV. The high refractive index transition layer is made of ZrO2, HfO2, Nb2O5 or Ta2O5, with a deposition thickness of 25-65 nm, a deposition rate of 0.05-0.15 nm / s, and an ion source assisted energy of 500-800 eV. The low-refractive-index surface passivation layer is made of Y2O3, Al2O3 or MgO, with a deposition thickness of 290-370 nm, a deposition rate of 0.1-0.2 nm / s, and an ion source-assisted energy of 500-800 eV. During the deposition process, the temperature of the optical fiber substrate is controlled to not exceed 120℃; (5) When depositing the moisture-proof protective layer M, a single-layer pure oxide structure, a single-layer mixed oxide structure, or a multi-layer gradient composite structure is adopted. a. The single-layer pure oxide structure adopts Al2O3, HfO2 or Y2O3; the deposition thickness is 100-130nm, the deposition rate is 0.1-0.2nm / s, and the ion source assisted energy is 500-800eV; b. The single-layer mixed oxide structure adopts a mixed layer of SiO2 and metal oxide, wherein the metal oxide is selected from at least one of Al2O3, ZrO2, HfO2, Y2O3, Sc2O3, La2O3, Ta2O5 and Nb2O5, and the deposition thickness is 100–130 nm. c. The multilayer gradient composite structure is a mixture of SiO2 and metal oxides with different component ratios arranged in multiple layers, with a single layer deposition thickness of 30–80 nm; or a multilayer pure oxide structure, with each pure oxide structure using Al2O3, HfO2 or Y2O3, and a single layer deposition thickness of 30–50 nm.
Citation Information
Patent Citations
A color separation element for visible light, laser, and mid-infrared bands using an all-dielectric thin film and its design method
CN107290814B
Intermediate infrared film for chalcogenide glass optical fiber end face and design method thereof
CN120195781A
Preparation method of porous full SiO2 laser reflection film
CN120505592A